Medical device and method of manufacturing the same
Patent Information
- Application Number
- CN202580021991.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-03-21
- Filing Date
- 2025-03-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]本发明是鉴于上述情况而完成的,目的在于提供一种具有润滑层的医疗用具及其制造方法,该润滑层具备维持良好的润滑性且耐久性(特别是滑动耐久性)提高的润滑层结构。
Smart Images

Figure CN123022445A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to medical devices and their manufacturing methods. Background Technology
[0002] For medical devices such as catheters and guidewires inserted into the body, excellent lubricity is required to reduce damage to blood vessels and other tissues and improve operator maneuverability. Therefore, methods for coating the substrate layer of medical devices with lubricating hydrophilic polymers have been developed and put into practical use. On the other hand, for such medical devices, it is also important to maintain the lubricating hydrophilic polymer on the substrate layer surface during operator use to ensure operability. Therefore, coatings formed from hydrophilic polymers require not only excellent lubricity but also durability against abrasion, scratching, and other loads.
[0003] From this perspective, Japanese Patent Application Publication No. 8-33704 (corresponding to US Patent No. 5670558) discloses a medical device in which a polymer solution is prepared by dissolving a water-soluble or water-swellable polymer in a solvent that swells the substrate of the medical device, the substrate of the medical device is immersed in the polymer solution to swell, and the polymer is further crosslinked or polymerized on the surface of the substrate layer to form a surface lubricating layer on the surface of the substrate layer.
[0004] According to the technology disclosed in the aforementioned documents, a surface lubricating layer that exhibits good lubricity can be fixed to a substrate. Summary of the Invention
[0005] The aforementioned literature discloses block copolymers, preferably comprising a hydrophilic portion exhibiting lubricity and an epoxy group portion, as water-soluble or water-swellable polymers. Furthermore, when using such block copolymers, a heating process can be used to crosslink or polymerize the block copolymer, forming a surface lubricating layer that is less prone to peeling.
[0006] On the other hand, as medical procedures become increasingly complex, the operation of medical devices sometimes lasts for longer periods. Therefore, even when treating lesions by passing through highly complex biological lumens, techniques that further improve the lubrication maintenance (durability) of the device surface compared to existing technologies are required to maintain good operability of the medical device for extended periods. More specifically, even when repeatedly sliding the medical device under harsh conditions (e.g., when repeatedly sliding the device to deliver it to the lesion site through areas with small bending radii, continuous bends in biological lumens, or narrow inner diameters of biological lumens), medical devices capable of maintaining high lubricity and excellent sliding durability are required.
[0007] Therefore, there is a need for technologies that can improve the durability (especially sliding durability) of the lubricating layer of medical devices and support complex and sophisticated medical procedures.
[0008] The present invention was made in view of the above circumstances, and its object is to provide a medical device having a lubricating layer and a method for manufacturing the same, wherein the lubricating layer has a structure that maintains good lubricity and improves durability (especially sliding durability).
[0009] The inventors of this application conducted in-depth research to solve the aforementioned problems. As a result, they discovered that by forming a lubricating layer with a specific lubrication layer structure, the aforementioned problems can be solved, thus completing this invention.
[0010] The above-mentioned problems can be solved by the present invention having the following structure, which includes the following modes and forms.
[0011] One aspect of the present invention is as follows: 1. Medical equipment, which includes: Substrate layer, and A lubricating layer supported on at least a portion of the aforementioned substrate layer and swelling upon contact with an aqueous solvent. The aforementioned lubricating layer comprises a polymer having structural unit A derived from a hydrophilic monomer. In the observed images of the lubricating layer during swelling, the surface of the lubricating layer has a mesh structure and multiple pores surrounded by the mesh structure. The above-mentioned mesh structure and the above-mentioned perforations satisfy either condition (1) or condition (2): (1) The average area of the above-mentioned holes is 1 μm when viewed from above. 2 The above, and the maximum area is 30μm 2 the following; (2) The average area of the above-mentioned holes is 1 μm when viewed from above. 2 The above, and the maximum area is greater than 30μm 2 The average mesh thickness of the above mesh structure is above 1 μm.
[0012] 2. In the medical device described in 1. above, preferably, the average area of the perforation when viewed from above is 1 to 10 μm. 2 The ratio of the maximum area of the above-mentioned apertures to the average mesh thickness of the above-mentioned mesh structure (the maximum area of the above-mentioned apertures (unit: μm)). 2 The average mesh thickness (in μm) of the above mesh structure is 20–50. 3. In the medical device described in 1. or 2. above, preferably, the average area of the perforation when viewed from above is 3 to 10 μm. 2 ; 4. In any one of the medical devices described in 1. to 3. above, it is preferred that the average area of the orifice, viewed from above, is 3 to 10 μm. 2 And the maximum area is greater than 30μm 2 And it is 100μm 2 The following is a ratio of the maximum area of the above-mentioned apertures to the average mesh thickness of the above-mentioned mesh structure (maximum area of the above-mentioned apertures (unit: μm)). 2 The average mesh thickness (in μm) of the above mesh structure is 20–50. 5. In any one of the medical devices described in 1. to 4. above, it is preferable that, in a 5000x magnification observation image of the lubricating layer when it is swollen, there are fewer than 5 needle-like crystals with a length of 1 μm or more on the surface of the lubricating layer; 6. In any one of the medical devices described in 1. to 5. above, preferably, the structural unit A derived from the hydrophilic monomer is a structural unit derived from at least one monomer selected from the group consisting of acrylic acid, acrylamide, N-methylacrylamide, N,N-dimethylacrylamide, N-ethylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide, N-(2-hydroxybutyl)acrylamide, N-vinyl-2-pyrrolidone, polyethylene glycol monoacrylate, polyethylene glycol monomethacrylate, alkoxy polyethylene glycol monoacrylate, and alkoxy polyethylene glycol monomethacrylate. 7. In any one of the medical devices described in 1 to 6 above, it is preferred that the lubricating layer comprises a copolymer having structural unit A derived from a hydrophilic monomer and structural unit B derived from a hydrophobic monomer having an epoxy group; 8. In the medical device described in 7 above, preferably, the structural unit B derived from the hydrophobic monomer having an epoxy group is a structural unit derived from at least one monomer selected from the group consisting of glycidyl acrylate, glycidyl methacrylate, 3,4-epoxycyclohexyl methyl acrylate, 3,4-epoxycyclohexyl methyl methacrylate, β-methyl glycidyl acrylate and β-methyl glycidyl methacrylate. 9. In the medical device described in 7 or 8 above, it is preferred that the copolymer contains the structural unit A derived from the hydrophilic monomer in a ratio of 5 to 50 moles relative to 1 mole of the structural unit B derived from the hydrophobic monomer having an epoxy group. 10. In any one of the medical devices described in 1. to 9. above, it is preferable that the sliding resistance value obtained by evaluating the sliding resistance value of the lubricating layer is less than 20 gf; 11. In any one of the medical devices described in 1. to 10. above, it is preferred that the lubricating layer is free of photopolymerization initiator and its residues; 12. In any one of the medical devices described in 1. to 11. above, it is preferred that the lubricating layer is formed by curing with an electron beam; 13. In any one of the medical devices described in 1. to 12. above, it is preferred that the medical device is a catheter, stent, or guidewire.
[0013] Other aspects of the present invention are as follows: 14. A method for manufacturing a medical device, comprising: A coating liquid is applied to at least a portion of a substrate layer to form a precursor layer on at least a portion of the substrate layer. The coating liquid comprises a polymer having structural unit A derived from a hydrophilic monomer and a solvent. An electron beam is used to irradiate the precursor layer with an irradiation dose greater than 0 kGy and less than 500 kGy to form a lubricating layer on the substrate layer that swells upon contact with an aqueous solvent. In the observation images of the aforementioned lubricating layer during swelling, the surface of the lubricating layer has a mesh structure and multiple pores surrounded by the mesh structure. The above-mentioned mesh structure and the above-mentioned perforations satisfy either condition (1) or condition (2): (1) The average area of the above-mentioned holes is 1 μm when viewed from above. 2 The above, and the maximum area is 30μm 2 the following; (2) The average area of the above-mentioned holes is 1 μm when viewed from above. 2 The above, and the maximum area is greater than 30μm 2 The average mesh thickness of the above mesh structure is above 1 μm.
[0014] 15. In the method for manufacturing the medical device described in 14 above, it is preferable to irradiate the precursor layer with an electron beam at an irradiation dose greater than 5 kGy and less than 200 kGy. Attached Figure Description
[0015] [ Figure 1 ] Figure 1 This is a SEM image of the sample used for surface observation in Comparative Example 1.
[0016] [ Figure 2 ] Figure 2 This is a SEM image of the sample used for surface observation in Comparative Example 2.
[0017] [ Figure 3 ] Figure 3 This is an SEM image of the sample used for surface observation in Example 1.
[0018] [ Figure 4 ] Figure 4 This is an SEM image of the sample used for surface observation in Example 2.
[0019] [ Figure 5 ] Figure 5 This is an SEM image of the sample used for surface observation in Example 3.
[0020] [ Figure 6 ] Figure 6 This is a SEM image of the sample used for surface observation in Comparative Example 3.
[0021] [ Figure 7 ] Figure 7 This is a SEM image of the sample used for surface observation in Comparative Example 4.
[0022] [ Figure 8 ] Figure 8 This is an SEM image of the sample used for surface observation in Example 4.
[0023] [ Figure 9 ] Figure 9 This is an SEM image of the sample used for surface observation in Example 5.
[0024] [ Figure 10 ] Figure 10 The image is obtained by binarizing the SEM image of the sample used for surface observation in Example 2 (binarized image).
[0025] [ Figure 11 ] Figure 11 Yes Figure 10 The image obtained by edge processing of a binarized image (edge-processed image). Detailed Implementation
[0026] One aspect of the present invention relates to a medical device comprising: a substrate layer, and a lubricating layer supported on at least a portion of the substrate layer and swelling upon contact with an aqueous solvent, the lubricating layer comprising a polymer having structural unit A derived from a hydrophilic monomer, and in an observation image of the lubricating layer during swelling, the surface of the lubricating layer having a mesh structure and a plurality of pores surrounded by the mesh structure, the mesh structure and the pores satisfying either condition (1) or condition (2): (1) The average area of the above-mentioned holes is 1 μm when viewed from above. 2 The above, and the maximum area is 30μm 2 the following; (2) The average area of the above-mentioned holes is 1 μm when viewed from above.2 The above, and the maximum area is greater than 30μm 2 The average mesh thickness of the above mesh structure is above 1 μm.
[0027] Another aspect of the present invention relates to a method for manufacturing a medical device, comprising: applying a coating liquid to at least a portion of a substrate layer; forming a precursor layer on at least a portion of the substrate layer; the coating liquid comprising a polymer having structural unit A derived from a hydrophilic monomer and a solvent; irradiating the precursor layer with an electron beam at an irradiation dose greater than 0 kGy and less than 500 kGy; forming a lubricating layer on the substrate layer that swells upon contact with an aqueous solvent; and, in an observation image of the lubricating layer during swelling, the surface of the lubricating layer having a mesh structure and a plurality of pores surrounded by the mesh structure, wherein the mesh structure and the pores satisfy either condition (1) or condition (2). (1) The average area of the above-mentioned holes is 1 μm when viewed from above. 2 The above, and the maximum area is 30μm 2 the following; (2) The average area of the above-mentioned holes is 1 μm when viewed from above. 2 The above, and the maximum area is greater than 30μm 2 The average mesh thickness of the above mesh structure is above 1 μm.
[0028] This configuration enables the provision of medical devices with a lubricating layer that maintains good lubricity and improves durability (especially sliding durability).
[0029] In this specification, the range "X~Y" includes both X and Y, meaning "above X and below Y". Additionally, "X and / or Y" means at least one of X and Y, including X alone, Y alone, and combinations of X and Y. In this specification, the term "(meth)acrylic" includes both acrylic acid and methacrylic acid. Therefore, for example, the term "(meth)acrylic acid" includes both acrylic acid and methacrylic acid. Similarly, the term "(meth)acryloyl" includes both acryloyl and methacryloyl. Therefore, for example, the term "(meth)acryloyl" includes both acryloyl and methacryloyl. Furthermore, similarly, the term "(meth)acrylate" includes both acrylate and methacrylate. For example, the term "(meth)acrylate alkoxyalkyl ester" includes both alkoxyalkyl acrylate and alkoxyalkyl methacrylate.
[0030] In this specification, when a structural unit is specified as "derived" from a monomer, it means that the structural unit is a structural unit generated by a condensation reaction of the reactive groups of the corresponding monomer, a structural unit generated by the cleavage of the epoxy groups of the corresponding monomer, and / or a structural unit generated by the cleavage of the olefinic unsaturated groups (polymeric unsaturated double bonds) of the corresponding monomer.
[0031] Unless otherwise specified, the determination of operation and physical properties shall be carried out at room temperature (20-25°C) and relative humidity (40-60%RH).
[0032] <Medical Equipment> One aspect of the present invention relates to a medical device comprising: a substrate layer, and a lubricating layer supported on at least a portion of the substrate layer and swelling upon contact with an aqueous solvent. Furthermore, the lubricating layer of the medical device of the present invention comprises a polymer having structural unit A derived from a hydrophilic monomer. In an observation image of the lubricating layer during swelling, the surface of the lubricating layer has a mesh structure and a plurality of pores surrounded by the mesh structure, wherein the mesh structure and the pores satisfy either condition (1) or condition (2): (1) The average area of the above-mentioned holes is 1 μm when viewed from above. 2 The above, and the maximum area is 30μm 2 the following; (2) The average area of the above-mentioned holes is 1 μm when viewed from above. 2 The above, and the maximum area is greater than 30μm 2 The average mesh thickness of the above-described mesh structure is 1 μm or more. Hereinafter, the medical device having the above-described structure will also be referred to as "the medical device of the present invention" or "medical device".
[0033] In this specification, the lubricating layer that swells upon contact with an aqueous solvent is also referred to as "the lubricating layer of the present invention" or "lubricating layer". Furthermore, the mesh structure observed in the observation image of the lubricating layer during swelling is also referred to as "the mesh structure of the present invention" or "mesh structure". Additionally, in this specification, the plurality of pores surrounded by the aforementioned mesh structure observed in the observation image of the lubricating layer during swelling is also referred to as "pores of the present invention" or "pores". Furthermore, in this specification, the aforementioned condition (1) is also referred to as "condition (1) of the present invention" or "condition (1)". Furthermore, in this specification, the aforementioned condition (2) is also referred to as "condition (2) of the present invention" or "condition (2)".
[0034] In the medical device of the present invention, the surface of the lubricating layer has a mesh structure observed in an image of the lubricating layer during swelling, and a plurality of pores surrounded by the mesh structure, wherein the mesh structure and the pores satisfy a specific condition (1) or condition (2). By giving the lubricating layer such a specific lubricating layer structure, the medical device of the present invention not only has good lubricity when wet (e.g., when in contact with bodily fluids such as blood, aqueous liquids such as saline; hereinafter the same) but also excellent durability (especially sliding durability).
[0035] The mechanism by which the medical device of the present invention achieves the aforementioned effects is not fully understood and is not bound by any theory, but is speculated to be the following: The pores formed on the surface of the lubricating layer of the present invention have an average area of 1 μm during swelling. 2 The above (conditions (1) and (2)). In this way, the lubricating layer has an average area of 1 μm. 2 The aforementioned pores allow for the absorption of sufficient water (water molecules) when wetted, thus providing excellent lubricity (smoothness). In contrast, the average area of the pores is less than 1 μm. 2 In such cases, sufficient water (water molecules) cannot be absorbed into the pores, resulting in decreased swelling of the lubricating layer and the inability to achieve excellent lubricity (smoothness).
[0036] In addition, as specified in condition (1), the maximum area of the pores formed in the lubricating layer is 30 μm. 2 In the following cases, the mesh structure is formed densely (with high density), the overall strength of the lubrication layer structure increases, and the durability of the lubrication layer (especially its sliding durability) is improved. On the other hand, as specified in condition (2), the maximum area of the pores is greater than 30 μm. 2 In this case, the mesh structure becomes coarser (density decreases), but at this point, when the average mesh thickness is above 1 μm, the strength of the mesh structure itself increases, resulting in improved durability of the lubrication layer (especially sliding durability). Conversely, when the maximum area of the pores is greater than 30 μm... 2 Furthermore, when the average mesh thickness is less than 1 μm, although good lubricity (smoothness) can be achieved due to the size of the pores, the strength of the mesh structure itself decreases due to the excessively fine mesh thickness, resulting in a decrease in the durability of the lubricating layer (especially its sliding durability). Specifically, it is speculated that when the average mesh thickness is less than 1 μm, the polymer forming the lubricating layer is prone to detachment during sliding, leading to a decrease in the durability of the lubricating layer (especially its sliding durability).
[0037] In summary, by providing a lubricating layer structure with a mesh structure and pores that satisfy condition (1) or condition (2), the medical device of the present invention can maintain excellent lubricity and exhibit excellent lubricity maintenance (sliding durability) even under harsh conditions where the medical device is repeatedly slidable (e.g., when repeatedly slidable to deliver the medical device to the lesion site through a portion of a biological lumen with a small radius of curvature, a portion of a biological lumen with continuous curvature, or a portion of a biological lumen with a narrow inner diameter). Therefore, according to the present invention, it is possible to provide a medical device having a lubricating layer and a method for manufacturing the same, wherein the lubricating layer has a lubricating layer structure that maintains good lubricity and improves durability (especially sliding durability).
[0038] The preferred embodiments of the present invention will be described below. It should be noted that the present invention is not limited to the following embodiments, and various modifications can be made within the scope of the claims. Furthermore, the embodiments described in this specification can be combined in any way to form other embodiments.
[0039] Throughout this specification, unless otherwise specified, singular expressions should be understood to include the concept of their plural forms. Therefore, unless otherwise specified, articles in the singular form (e.g., "a," "an," "the," etc. in the English context) should be understood to include the concept of their plural forms. Furthermore, unless otherwise specified, the terminology used in this specification should be understood to be used in the meaning commonly understood in the art. Therefore, unless otherwise defined, all technical and technical terms used in this specification have the same meaning as commonly understood by those skilled in the art to which this invention pertains. In cases of conflict, this specification (including definitions) takes precedence.
[0040] [Substrate Layer (Substrate)] The substrate layer (substrate) used in this invention can be made of any material, which can be appropriately selected according to the application. Specifically, the materials constituting (forming) the substrate layer include metallic materials, polymeric materials, ceramics, etc. Here, the substrate layer may be wholly (entirely) composed of any of the above-mentioned materials, or it may have a structure in which the surface of the core of the substrate layer composed of any of the above-mentioned materials is coated (coated) with other of the above-mentioned materials in an appropriate manner to form a substrate surface layer. Examples of the latter include: coating a metal material onto the surface of a substrate core made of a resin material or similar material using a suitable method (plating, metal evaporation, sputtering, or other conventionally known methods), thereby forming a substrate surface layer; coating a polymer material softer than the reinforcing material such as a metal material onto the surface of a substrate core made of a hard reinforcing material such as a metal or ceramic material using a suitable method (impregnation, spraying, coating, printing, or other conventionally known methods); or combining the reinforcing material of the substrate core with the polymer material of the substrate surface layer (through appropriate reaction treatment), thereby forming a substrate surface layer. Therefore, the substrate core can also be a multilayer structure formed by stacking multiple layers of different materials, or a structure (composite) formed by connecting components of different materials together in a medical device. Furthermore, other intermediate layers can be further formed between the substrate core and the substrate surface layer. In addition, the surface layer of the substrate can also be a multilayer structure made by stacking different materials, or a structure (composite) made by connecting the various parts of a medical device made of different materials.
[0041] Among the materials constituting (forming) the aforementioned substrate layer, there are no particular restrictions on the metallic materials used; commonly used metallic materials for medical devices such as catheters, stents, and guidewires can be employed. Specifically, examples include various stainless steels (SUS) such as SUS304, SUS316, SUS316L, SUS420J2, and SUS630, as well as gold, platinum, silver, copper, nickel, cobalt, titanium, iron, aluminum, tin, or various alloys such as nickel-titanium (Ni-Ti) alloys, nickel-cobalt (Ni-Co) alloys, cobalt-chromium (Co-Cr) alloys, and zinc-tungsten (Zn-W) alloys. One or more of these materials can be used individually. The most suitable metallic material for the intended use as the substrate layer for catheters, stents, guidewires, etc., should be selected from the aforementioned metallic materials.
[0042] In addition, there are no particular restrictions on the materials used to form the above-mentioned substrate layer, and polymeric materials (resin materials or elastomer materials) can be used, such as those commonly used in medical devices such as catheters, stents, and guidewires. Specifically, examples include polyamide resins, linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), high-density polyethylene (HDPE), modified polyethylene and other polyethylene resins, polyolefin resins such as polypropylene resins, modified polyolefin resins, cyclic polyolefin resins, epoxy resins, polyurethane resins, diallyl phthalate resins (allyl resins), polycarbonate resins, polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene (ETFE) and other fluoropolymers, amino resins (urea-formaldehyde resins, melamine resins, benzoguanamine resins), polyethylene terephthalate resins, polybutylene terephthalate resins and other polyester resins, polystyrene and other styrene resins, acrylic resins, polyacetal resins, vinyl acetate resins, phenolic resins, vinyl chloride resins (polyvinyl chloride (PVC)), silicone resins (silicone resins), polyether resins such as polyetheretherketone (PEEK), polyimide resins, etc. In addition, thermoplastic elastomers such as polyurethane elastomers, polyester elastomers, and polyamide elastomers (nylon elastomers) can also be used as substrate materials. They can be used individually or in combination of two or more. Among the aforementioned polymer materials, the most suitable polymer material should be selected for the substrate layer of the catheter, stent, guidewire, etc., intended for use.
[0043] In addition, there are no particular restrictions on the shape of the above-mentioned substrate layer. It can be appropriately selected as sheet-like, wire-like, tubular, etc., depending on the application.
[0044] [Lubricating layer] A lubricating layer is formed (supported) on at least a portion of the aforementioned substrate layer (substrate). The reason for forming (supporting) the lubricating layer on at least a portion of the surface of the substrate layer is that, in medical devices such as catheters, stents, and guidewires intended for use, it is not necessary for the entire surface of these medical devices to be lubricated when wet; only the surface portion (sometimes a portion, sometimes all) where lubrication when wet is required is supported by the lubricating layer. Therefore, for example, if the substrate layer is tubular, the lubricating layer may have the following forms: a form formed entirely on the outer surface of the substrate layer; a form formed entirely on the inner surface of the substrate layer; a form formed from a portion of the outer and inner surfaces of the substrate layer with the same or different forms; a form formed from a portion of the outer or inner surface of the substrate layer, etc. Furthermore, if the substrate layer is filamentous, the lubricating layer may have the following forms: a form formed entirely on the outer surface of the substrate layer; a form formed from a portion of the outer surface of the substrate layer, etc. In addition, when the substrate layer is sheet-like, the lubricating layer includes the following forms: a form formed entirely on one side of the substrate layer; a form formed entirely on both sides of the substrate layer; a form formed from portions of both sides of the substrate layer with the same or different forms; a form formed from a portion of one side of the substrate layer, etc.
[0045] The lubricating layer of the present invention comprises a polymer having structural unit A derived from a hydrophilic monomer, as detailed below, and swells upon contact with an aqueous solvent. Here, there are no particular limitations on the aqueous solvent; examples include water (RO water, pure water, ion-exchanged water, distilled water, etc.), physiological saline, phosphate-buffered saline (PBS), etc. It should be noted that in this specification, "observation image of the lubricating layer when it swells" refers to an observation image of the lubricating layer in a swollen state after contact with water. Here, "swelling state" refers to a state in which the lubricating layer absorbs the aqueous solvent, resulting in an increase in the volume and expansion of the lubricating layer. Specifically, it refers to a state in which, upon contact with an aqueous solvent, the aqueous solvent (water molecules, etc.) is absorbed into the molecular chains of the polymer constituting the lubricating layer, the lubricating layer softens, and its volume increases. Thus, in order to form a lubricating layer that swells upon contact with an aqueous solvent, the lubricating layer only needs to comprise a polymer having structural unit A derived from a hydrophilic monomer, as described below.
[0046] The lubricating layer of the present invention has a mesh structure on its surface and a plurality of pores surrounded by the mesh structure. Here, the mesh structure and the pores can be observed in an image of the lubricating layer during swelling. In the lubricating layer, the mesh structure has a structure formed by the three-dimensional bonding of polymers constituting the lubricating layer (three-dimensional mesh structure). Furthermore, the pores are spatial regions surrounded by the aforementioned mesh structure and are created due to the formation of the mesh structure. That is, the mesh structure in the lubricating layer can function as a framework for forming the pores.
[0047] One feature of the medical device of the present invention is that, when the surface of the swollen lubricating layer is observed from above, the observed mesh structure and pores have a specific structure. The structure (area, mesh thickness) of the mesh structure and pores is analyzed based on the observation image of the lubricating layer during swelling. Specifically, it is determined by analyzing the SEM image obtained by the method described in the "[Analysis of Mesh Structure]" section of the embodiment using the method described therein.
[0048] In the lubricating layer of the present invention, the mesh structure and the pores satisfy either condition (1) or condition (2): (1) The average area of the pore is 1 μm when viewed from above. 2 The above, and the maximum area is 30μm 2 the following; (2) The average area of the pores when viewed from above is 1 μm. 2 The above, and the maximum area is greater than 30μm 2 The average mesh thickness of the mesh structure is over 1 μm; The above condition (1) is a form with relatively small pores and a dense (high-density) mesh structure, and the above condition (2) is a form with relatively large pores and a coarse mesh structure (mesh thickness). By satisfying either condition (1) or condition (2), the medical device of the present invention can maintain excellent lubricity and exhibit excellent lubricity maintenance (sliding durability).
[0049] Conditions (1) and (2): Average area of the hole In either condition (1) or condition (2), the average area of the pore, viewed from above, is 1 μm. 2 The above. The average area of the pores is preferably 2 μm. 2 The above, preferably 3μm 2 The above is particularly preferred, with 5μm. 2 The larger the average area of the pores, the easier it is for water (water molecules) to be drawn into the pores when wet, thus improving lubricity (smoothness). On the other hand, there is no particular upper limit to the average area of the pores, but for example, it can be 30 μm. 2 Below that, 20μm is also possible.2 Below that, 10μm is also possible. 2 Below that, 7μm is also possible. 2 Therefore, the average area of the pores is, for example, 1–30 μm. 2 It can also be 1–20 μm 2 It can also be 1–10 μm 2 Furthermore, the average area of the pores is preferably 2–10 μm. 2 More preferably 3–10 μm 2 More preferably 5–10 μm 2 Especially preferred is 5-7 μm 2 .
[0050] Condition (1): Maximum area of the hole In condition (1), the maximum area of the hole when viewed from above is 30 μm. 2 The maximum area of the aperture is preferably 25 μm. 2 Below, 20 μm is more preferred. 2 The smaller the maximum area of the pores, the denser the network structure (forming a high density), resulting in higher overall strength of the lubrication layer structure and improved durability (especially sliding durability) of the lubrication layer. On the other hand, there is no particular lower limit to the maximum area of the pores, but for example, it can be greater than 1 μm. 2 It can also be 5μm 2 The above can also be 10μm. 2 Therefore, in condition (1), the maximum area of the pore is, for example, greater than 1 μm. 2 And it is 30μm 2 The preferred values are 5–25 μm. 2 More preferably 10–20 μm 2 .
[0051] Condition (1): Average mesh thickness of the mesh structure Under condition (1), there is no particular limitation on the average value of the mesh thickness of the mesh structure. The average value of the mesh thickness of the mesh structure mainly contributes to the durability of the lubricating layer (especially the sliding durability), but this is because the maximum area of the holes satisfies the condition (1) above, thus forming a lubricating layer with sufficient durability. In condition (1), the average value of the mesh thickness of the mesh structure can be, for example, 0.01 to 12.8 μm (less than half the length of the long side of the observed image), 0.3 to 5 μm, or 0.5 to 3 μm.
[0052] Condition (2): Maximum area of the hole In condition (2), the maximum area of the hole when viewed from above is greater than 30 μm. 2The maximum area of the aperture is preferably 40 μm. 2 The above, more preferably 50μm 2 The larger the maximum area of the pores, the easier it is for water (water molecules) to be drawn into the pores when wet, thus improving lubricity (smoothness). On the other hand, there is no particular upper limit to the maximum area of the pores, but for example, it is 250 μm. 2 The area below (less than half the total area of the observed image) can also be 100μm. 2 Below that, 80μm is also possible. 2 Therefore, in condition (2), the maximum area of the aperture is, for example, greater than 30 μm. 2 And it is 250μm 2 Below that, it can also be greater than 30μm. 2 And it is 100μm 2 The preferred size is 40–100 μm. 2 More preferably 50–80 μm 2 .
[0053] Condition (2): Average mesh thickness of the mesh structure In condition (2), the average thickness of the mesh structure is 1 μm or more. The average thickness of the mesh structure is preferably 1.1 μm or more, more preferably 1.3 μm or more, and particularly preferably 1.4 μm or more. The larger the average thickness of the mesh structure (mesh thickness), the higher the strength of the mesh structure itself, and the better the durability (especially the sliding durability) of the lubricating layer. On the other hand, there is no particular upper limit to the average thickness of the mesh structure, but it can be, for example, 12.8 μm or less (less than half the length of the long side of the observed image), 5 μm or less, or 3 μm or less. Therefore, in condition (2), the average thickness of the mesh structure is, for example, 1 to 12.8 μm, preferably 1.1 to 5 μm, more preferably 1.3 to 5 μm, and particularly preferably 1.4 to 3 μm.
[0054] Maximum area of the aperture / average mesh thickness of the mesh structure In addition to satisfying either of the conditions (1) and (2) above, the lubricating layer (mesh structure and pores) involved in this invention preferably has a ratio of the maximum area of the pores to the average mesh thickness of the mesh structure (maximum area of the pores (unit: μm)). 2 The average mesh thickness (in μm) of the mesh structure is within the following range. It should be noted that in this specification, "the ratio of the maximum area of the aperture relative to the average mesh thickness of the mesh structure (maximum area of the aperture (in μm)") is used. 2The average value of the mesh thickness of the mesh structure (unit: μm) is also simply referred to as the "maximum area / average mesh thickness". That is, in addition to satisfying either of the above conditions (1) and (2), the average value of the maximum area / mesh thickness of the lubricating layer (mesh structure and pores) involved in this invention is preferably 20 to 50, more preferably 25 to 40, and particularly preferably 25.5 to 40. If the above ratio is within the above range, the mesh structure is formed with a moderately high density, and the lubricating layer can easily absorb a moderate amount of water (water molecules) in the pores when wet, thus achieving a balanced This invention effectively improves the durability and lubricity (smoothness) of the lubricating layer. It should be noted that the average value of the maximum area / mesh thickness is preferably within the above-mentioned range, but even if it exceeds this range, it can be fully utilized as long as it does not affect the effectiveness of the invention. For example, from the viewpoint of forming a lubricating layer with good lubricity (smoothness), the average value of the maximum area / mesh thickness can be greater than 1, or it can be less than 1. Regardless of the range of the average value of the maximum area / mesh thickness, the lubricating layer of the present invention has an average pore area of 1 μm. 2 The above ensures sufficient lubrication, but from the viewpoint of obtaining better lubrication (smoothness), the average value of maximum area / net thickness is preferably greater than 1.
[0055] Preferred Form The lubricating layer (mesh structure and apertures) of the present invention preferably satisfies the above-described condition (1) or condition (2), and further satisfies a combination of preferred ranges for the average and maximum areas of the apertures described above, the average mesh thickness of the mesh structure, and the average range of the maximum area / mesh thickness. For example, the lubricating layer (mesh structure and apertures) of the present invention preferably satisfies the above-described condition (1) or condition (2), and further satisfies at least one of the following: (i) The average area of the pores when viewed from above is 1–10 μm. 2 The average value of maximum area / net thickness is 20-50; (ii) The average area of the pores when viewed from above is 3–10 μm. 2 ; (iii) The average area of the pores when viewed from above is 3–10 μm. 2 And the maximum area is greater than 30μm 2 And it is 100μm 2 The average value for maximum area / net thickness is 20 to 50. (iv) The average area of the pores when viewed from above is 1–10 μm. 2 And the maximum area is 5–25 μm. 2 The average mesh thickness of the mesh structure is 0.3–5 μm; (v) The average area of the pores when viewed from above is 1–10 μm. 2 And the maximum area is 5–25 μm. 2 The average mesh thickness of the mesh structure is 0.5–3 μm; (vi) The average value of maximum area / net thickness is 25 to 40; (vii) The average area of the pores when viewed from above is 5–7 μm. 2 ; (viii) The average value of maximum area / net thickness is 25.5 to 40.
[0056] In other embodiments, the lubricating layer (mesh structure and pores) of the present invention preferably satisfies the above-described condition (2). Furthermore, the lubricating layer (mesh structure and pores) of the present invention preferably satisfies the above-described condition (2), and further satisfies at least one of the forms (i) to (iii) and (vi) to (viii) described above. More preferably, the lubricating layer (mesh structure and pores) of the present invention satisfies the above-described condition (2), and further satisfies at least one of the forms (ii), (iii), (vii), and (viii) described above.
[0057] The medical device of the present invention comprises a lubricating layer having the specific lubricating layer structure described above. As detailed below, the area of each pore in such a lubricating layer structure and the mesh thickness of the mesh structure can be controlled by the composition of the polymer constituting the lubricating layer, curing conditions, etc.
[0058] Polymers possessing structural unit A derived from hydrophilic monomers The lubricating layer comprises a polymer having structural unit A derived from a hydrophilic monomer. The hydrophilic monomer constituting the polymer swells upon contact with bodily fluids (e.g., blood, urine) and aqueous solvents, imparting smoothness (lubricity) to the lubricating layer. Therefore, by introducing such structural unit A derived from a hydrophilic monomer into the polymer, the lubricating layer formed using this polymer exhibits excellent smoothness (lubricity), reducing friction when medical devices come into contact with the walls of biological cavities such as blood vessels. In this specification, "hydrophilic monomer" is also simply referred to as "the hydrophilic monomer of this invention" or simply "hydrophilic monomer". Furthermore, in this specification, "structural unit A derived from a hydrophilic monomer" is also simply referred to as "structural unit A of this invention" or simply "structural unit A". Additionally, in this specification, "polymer having structural unit A derived from a hydrophilic monomer" is also simply referred to as "the polymer of this invention" or simply "polymer".
[0059] As the hydrophilic monomer constituting the polymer, it can be any monomer as long as it exhibits lubricity in bodily fluids and aqueous solvents. Preferably, the hydrophilic monomer is a material that exhibits a swelling rate of 200% or more when a lubricating layer is formed from a polymer having structural unit A derived from the hydrophilic monomer. That is, in this invention, the polymer having structural unit A derived from the hydrophilic monomer is preferably a material whose lubricating layer formed using the polymer exhibits a swelling rate of 200% or more. It should be noted that, in this specification, the swelling rate of the lubricating layer is a value measured according to the method described in [Determination of Swelling Rate] of the following examples.
[0060] Polymers having structural unit A derived from hydrophilic monomers are more preferably materials exhibiting a swelling rate of 500% or more when forming a lubricating layer, and particularly preferably materials exhibiting a swelling rate of 800% or more when forming a lubricating layer. Furthermore, polymers having structural unit A derived from hydrophilic monomers are preferably materials in which a portion of the lubricating layer does not dissolve when wetted. Therefore, polymers having structural unit A derived from hydrophilic monomers are preferably materials exhibiting a swelling rate of less than 1500% when forming a lubricating layer, and particularly preferably materials exhibiting a swelling rate of less than 1300% when forming a lubricating layer. Therefore, polymers having structural unit A derived from hydrophilic monomers are preferably materials exhibiting a swelling rate of 200% or more and less than 1500% when forming a lubricating layer, more preferably materials exhibiting a swelling rate of 500% or more and less than 1500%, and particularly preferably materials exhibiting a swelling rate of 800% or more and less than 1300%.
[0061] That is, the swelling ratio of the lubricating layer involved in this invention is preferably 200% or more and less than 1500%, more preferably 500% or more and less than 1500%, and particularly preferably 800% or more and less than 1300%. In this way, if the swelling ratio of the lubricating layer is 200% or more, the lubricating layer can swell sufficiently when in contact with bodily fluids (e.g., blood, urine) or aqueous solvents, and the lubricity (smoothness) is further improved. Furthermore, if the swelling ratio of the lubricating layer is less than 1500%, the lubricating layer can maintain sufficient film strength, and the durability is further improved. Therefore, for lubricating layers with swelling ratios within the above-mentioned range, the balance between lubricity and durability is further improved.
[0062] Examples of such hydrophilic monomers include acrylic acid, acrylamide, methacrylamide, N-methacrylamide, N-methylmethacrylamide, N,N-dimethylacrylamide (DMAA), N,N-dimethylmethacrylamide, N-ethylacrylamide, N-ethylmethacrylamide, N,N-diethylacrylamide (DEAA), N,N-diethylmethacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, and N,N- Dimethylaminoethyl acrylate, N,N-dimethylaminoethyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide, N-(2-hydroxybutyl)acrylamide, N-vinyl-2-pyrrolidone (1-vinyl-2-pyrrolidone) (VP), polyethylene glycol monoacrylate, polyethylene glycol monomethacrylate, alkoxy polyethylene glycol monoacrylate and alkoxy polyethylene glycol monomethacrylate, etc. From the perspectives of further imparting lubricity to the lubricating layer, ease of synthesis, and operability, the hydrophilic monomer preferably includes those selected from acrylic acid, acrylamide, N-methylacrylamide, N,N-dimethylacrylamide, N-ethylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide, N-(2-hydroxybutyl)acrylamide, N-vinyl- The component comprises at least one of the following groups: 2-pyrrolidone, polyethylene glycol monoacrylate, polyethylene glycol monomethacrylate, alkoxy polyethylene glycol monoacrylate, and alkoxy polyethylene glycol monomethacrylate; more preferably, it comprises at least one of the following groups: acrylic acid, acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and N-vinyl-2-pyrrolidone; further preferably, acrylamide, N,N-dimethylacrylamide, or N-vinyl-2-pyrrolidone; and particularly preferably, N,N-dimethylacrylamide or N-vinyl-2-pyrrolidone. The structural unit A derived from the hydrophilic monomer may be composed of only one of the above-mentioned hydrophilic monomers, or it may be composed of two or more of the above-mentioned hydrophilic monomers.
[0063] Specifically, in one embodiment of the present invention, structural unit A derived from the hydrophilic monomer is a structural unit derived from at least one monomer selected from the group consisting of acrylic acid, acrylamide, N-methylacrylamide, N,N-dimethylacrylamide, N-ethylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide, N-(2-hydroxybutyl)acrylamide, N-vinyl-2-pyrrolidone, polyethylene glycol monoacrylate, polyethylene glycol monomethacrylate, alkoxy polyethylene glycol monoacrylate, and alkoxy polyethylene glycol monomethacrylate. In one embodiment of the present invention, structural unit A derived from the hydrophilic monomer is a structural unit derived from at least one monomer selected from the group consisting of acrylic acid, acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and N-vinyl-2-pyrrolidone. In one embodiment of the present invention, structural unit A derived from the hydrophilic monomer is derived from acrylamide, N,N-dimethylacrylamide, or N-vinyl-2-pyrrolidone.
[0064] Regarding the content (composition) of structural unit A derived from hydrophilic monomers constituting the polymer of the present invention, when the total of all structural units constituting the polymer is set to 100 mol%, it is preferably 80 mol% or more. When the total of all structural units constituting the polymer is set to 100 mol%, the content (composition) of the aforementioned structural unit A may also be 80 mol% or more and less than 100 mol%, or 90 mol% or more and less than 100 mol%, or 100 mol%. That is, the polymer of the present invention may be composed solely of structural unit A derived from hydrophilic monomers, or it may contain other structural units besides structural unit A derived from hydrophilic monomers.
[0065] (Other structural units) Other monomers constituting other structural units, besides the hydrophobic monomers with epoxy groups described in detail below, include 4-hydroxybutyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 1,4-cyclohexanediethanol mono(meth)acrylate, 1-chloro-2-hydroxypropyl (meth)acrylate, diethylene glycol mono(meth)acrylate, 1,6-hexanediol mono(meth)acrylate, pentaerythritol tetramethyl methacrylate, etc. Trimethacrylate, pentaerythritol pentamethacrylate, neopentyl glycol monomethacrylate, trimethylolpropane dimethacrylate, trimethylolethane dimethacrylate, 2-hydroxy-3-phenyloxypropyl methacrylate, 4-hydroxycyclohexyl methacrylate, 2-hydroxy-3-phenyloxy methacrylate, 4-hydroxycyclohexyl methacrylate, cyclohexanediol monomethacrylate, adipic acid, glutaric acid, triethylene glycol, tripropylene glycol, etc. These other structural units can be composed of only one other monomer, or they can be composed of two or more other monomers.
[0066] (Derived from structural unit B of a hydrophobic monomer with an epoxy group) The polymer forming the lubricating layer is preferably a copolymer that, in addition to having the structural unit A derived from the hydrophilic monomer described above, further has a structural unit B derived from a hydrophobic monomer with an epoxy group (hydrophobic monomer). That is, the lubricating layer of the present invention preferably comprises a copolymer having the structural unit A derived from the hydrophilic monomer described above and a structural unit B derived from a hydrophobic monomer with an epoxy group. In this specification, "hydrophobic monomer with an epoxy group" is also simply referred to as "the hydrophobic monomer of the present invention" or "hydrophobic monomer". Similarly, in this specification, "structural unit B derived from a hydrophobic monomer with an epoxy group" is also simply referred to as "structural unit B of the present invention" or "structural unit B". Furthermore, in this specification, "a copolymer having structural unit A derived from a hydrophilic monomer and structural unit B derived from a hydrophobic monomer with an epoxy group" is also simply referred to as "the copolymer of the present invention" or "copolymer".
[0067] The hydrophobic monomers constituting the copolymers of this invention have epoxy groups as reactive groups. When a copolymer incorporating structural unit B (hydrophobic site) derived from a hydrophobic monomer with epoxy groups is irradiated with an electron beam, the molecular bonds of the hydrophobic sites (especially epoxy groups) are preferentially cleaved due to the energy of the electron beam, forming multiple free radicals (crosslinking points). Therefore, the free radicals generated during electron beam irradiation react with the hydrophobic sites within the same copolymer and with the hydrophobic sites of adjacent copolymers, causing the copolymer molecular chains to bond together at multiple sites. Thus, when a lubricating layer containing the copolymers of this invention is irradiated with an electron beam, the copolymers form a crosslinked structure (three-dimensional mesh structure), further improving the film strength of the lubricating layer. Furthermore, it is presumed that the mesh structure and pores of this invention are formed in the lubricating layer at this time, either accompanying the formation of such a crosslinked structure or their formation is promoted. Such crosslinking reactions induced by electron beam irradiation may also occur in structural unit A (hydrophobic site) derived from a hydrophilic monomer, but the hydrophobic sites (especially epoxy groups) are more prone to this reaction. Therefore, from the viewpoint that the network structure and pores in the lubricating layer of the present invention can be easily controlled into a suitable structure, the lubricating layer preferably comprises a copolymer having structural unit B derived from a hydrophobic monomer having an epoxy group.
[0068] Furthermore, when a copolymer incorporating structural unit B (hydrophobic site) derived from a hydrophobic monomer with an epoxy group is irradiated with ultraviolet (UV) light, the photopolymerization initiator absorbs the UV light to form acidic species. These acidic species cause the hydrophobic sites (especially epoxy groups) to open, forming oxonium cations. Therefore, when the copolymer is irradiated with UV light, these oxonium cations react with the hydrophobic sites (especially epoxy groups) within the same copolymer and with the hydrophobic sites (especially epoxy groups) of adjacent copolymers, causing the copolymer molecular chains to bond together at multiple sites. Thus, when the lubricating layer containing the copolymer of the present invention is irradiated with UV light, the copolymers form a cross-linked structure (three-dimensional mesh structure), further improving the film strength of the lubricating layer. It is also presumed that the mesh structure and pores of the present invention are formed in the lubricating layer at this time, either accompanying the formation of such a cross-linked structure or their formation is promoted. Such a cross-linking reaction induced by UV irradiation may also occur in structural unit A (hydrophobic site) derived from a hydrophilic monomer using acidic species formed by a photopolymerization initiator, but the hydrophobic sites (especially epoxy groups) are more prone to this reaction. Therefore, from the viewpoint that the network structure and pores in the lubricating layer of the present invention can be easily controlled into a suitable structure, the lubricating layer preferably comprises a copolymer having structural unit B derived from a hydrophobic monomer having an epoxy group.
[0069] The hydrophobic monomer can be any compound that has an epoxy group, and there are no particular limitations; known compounds can be used. Specifically, considering the stabilization of intramolecular free radicals generated during electron beam irradiation, facilitating subsequent crosslinking reactions, and the stabilization of polymerizable active species (such as oxonium cations) generated during ultraviolet irradiation, facilitating subsequent crosslinking reactions, the hydrophobic monomer with an epoxy group preferably includes at least one selected from the group consisting of glycidyl acrylate, glycidyl methacrylate (GMA), 3,4-epoxycyclohexyl acrylate, 3,4-epoxycyclohexyl methacrylate, β-methyl glycidyl acrylate, and β-methyl glycidyl methacrylate. Glycidyl (meth)acrylate is more preferred, and glycidyl methacrylate is particularly preferred, considering its ability to further promote crosslinking reactions and ease of manufacture. Structural unit B derived from the hydrophobic monomer may consist of only one of the above-mentioned hydrophobic monomers, or it may consist of two or more of the above-mentioned hydrophobic monomers.
[0070] Specifically, in one embodiment of the present invention, structural unit B derived from an epoxy-based hydrophobic monomer is a structural unit derived from at least one monomer selected from the group consisting of glycidyl acrylate, glycidyl methacrylate, 3,4-epoxycyclohexyl methyl acrylate, 3,4-epoxycyclohexyl methyl methacrylate, β-methyl glycidyl acrylate, and β-methyl glycidyl methacrylate. In one embodiment of the present invention, structural unit B derived from an epoxy-based hydrophobic monomer is a structural unit derived from glycidyl acrylate or glycidyl methacrylate. In one embodiment of the present invention, structural unit B derived from an epoxy-based hydrophobic monomer is a structural unit derived from glycidyl methacrylate.
[0071] The copolymer can be a random copolymer having structural unit A derived from a hydrophilic monomer and structural unit B derived from a hydrophobic monomer with an epoxy group, or it can be a block copolymer having structural unit A derived from a hydrophilic monomer and structural unit B derived from a hydrophobic monomer with an epoxy group. Preferably, the copolymer is a block copolymer having blocks formed from hydrophilic monomers and blocks formed from hydrophobic monomers with epoxy groups (a block copolymer of hydrophilic monomers and hydrophobic monomers with epoxy groups). The block copolymer, with its blocks formed from hydrophilic monomers, can further improve the swelling properties of the lubricating layer. Furthermore, the block copolymer, with its blocks formed from hydrophobic monomers, increases the probability of cross-linking reactions between the hydrophobic monomers when irradiated by active energy rays such as electron beams or ultraviolet light, thus further improving the durability of the lubricating layer. Therefore, if a block copolymer is used, better results can be obtained in terms of film strength and lubricity of the lubricating layer.
[0072] The ratio of structural unit A derived from the hydrophilic monomer to structural unit B derived from the epoxy-containing hydrophobic monomer in the copolymer is not particularly limited. Considering further improvements in lubricity (smoothness, slip resistance) and durability (especially slip resistance), the copolymer preferably contains structural unit A derived from the hydrophilic monomer in a ratio of 5 to 70 moles relative to 1 mole of structural unit B derived from the epoxy-containing hydrophobic monomer. More preferably, the copolymer contains structural unit A derived from the hydrophilic monomer in a ratio of 5 to 50 moles relative to 1 mole of structural unit B derived from the epoxy-containing hydrophobic monomer. Even more preferably, the copolymer contains structural unit A derived from the hydrophilic monomer in a ratio of 8 to 40 moles relative to 1 mole of structural unit B derived from the epoxy-containing hydrophobic monomer. Particularly preferred is that the copolymer contains structural unit A derived from the hydrophilic monomer in a ratio of 10 to 35 moles relative to 1 mole of structural unit B derived from the epoxy-containing hydrophobic monomer. By setting the ratio of structural unit B derived from hydrophobic monomers with epoxy groups to structural unit A derived from hydrophilic monomers within the above range in the copolymer, the lubricating layer can have high lubricity and exhibit excellent sliding durability.
[0073] Alternatively, the content (composition) of structural unit A derived from the hydrophilic monomer in the copolymer can also be as follows. For example, in one embodiment of the present invention, the content (composition) of structural unit A derived from the hydrophilic monomer is 80 mol% or more and less than 100 mol% relative to all structural units constituting the copolymer. In another embodiment of the present invention, the content (composition) of structural unit A derived from the hydrophilic monomer is 90 to 99 mol% relative to all structural units constituting the copolymer. If the content (composition) of structural unit A derived from the hydrophilic monomer is within the above range, the lubricating layer can exhibit high lubricity.
[0074] In the copolymers of the present invention, when other structural units (structural units C) are further present in addition to structural units A derived from hydrophilic monomers and structural units B derived from hydrophobic monomers having epoxy groups, the total content of all structural units constituting the copolymer is set to 100 mol%, and the total content of the above-mentioned structural units A and B is preferably 95 mol% or more (upper limit: less than 100 mol%). More preferably, the copolymers of the present invention are substantially composed of the above-mentioned structural units A and B (the content of structural unit C = greater than 0 mol% and less than 5 mol%). In this form, the copolymers of the present invention can improve the lubricity (surface lubricity) brought by the above-mentioned structural unit A and the durability (especially sliding durability) brought by the above-mentioned structural unit B in a balanced and good manner. More preferably, the copolymers of the present invention (preferably block copolymers) are composed only of the above-mentioned structural units A and B (the content of structural unit C = 0 mol%). It should be noted that, in the case where there are other structural units C in addition to the above-mentioned structural units A and B, compounds other than the hydrophobic monomers with epoxy groups exemplified in the above-mentioned (other structural units) item can be cited as monomers constituting other structural units C that can be included in the copolymer.
[0075] It should be noted that the copolymer having the above composition can be controlled by adjusting the charging ratio (molar ratio) of each monomer to the range described above. Therefore, the charging ratio (molar ratio) of the hydrophilic monomer to the hydrophobic monomer during the copolymer manufacturing stage is preferably within the range described above.
[0076] The composition (molar ratio) of the structural units of the copolymer can be determined, for example, by NMR analysis of the copolymer. 1 H-NMR measurement, 13 This can be confirmed by methods such as C-NMR determination. For example, the composition of each structural unit can be determined by measuring the copolymer solution. 1 The composition (molar ratio) of each structural unit is determined by the integral ratio of the signal intensities of each H-NMR spectrum.
[0077] In one embodiment of the present invention, the polymer constituting the lubricating layer is selected from any of the following substances: derived solely from acrylic acid, acrylamide, N-methylacrylamide, N,N-dimethylacrylamide, N-ethylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide, N-(2-hydroxybutyl)acrylamide, N-vinyl-2-pyrrolidone, polyethylene glycol monoacrylate, polyethylene glycol monomethacrylate, alkoxy polyethylene glycol monoacrylate, etc. A polymer comprising structural unit A of at least one hydrophilic monomer selected from the group consisting of monoacrylates and alkoxy polyethylene glycol monomethacrylates; a copolymer substantially composed of structural unit A derived from the hydrophilic monomer and structural unit B derived from at least one hydrophobic monomer selected from the group consisting of glycidyl acrylate, glycidyl methacrylate, 3,4-epoxycyclohexyl methyl acrylate, 3,4-epoxycyclohexyl methyl methacrylate, β-methyl glycidyl acrylate and β-methyl glycidyl methacrylate; and a copolymer composed solely of structural unit A derived from the hydrophilic monomer and structural unit B derived from the hydrophobic monomer. In one embodiment of the present invention, the polymer constituting the lubricating layer is selected from any of the following substances: a polymer composed solely of structural unit A derived from at least one hydrophilic monomer selected from the group consisting of acrylic acid, acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide and N-vinyl-2-pyrrolidone; a copolymer substantially composed of structural unit A derived from the above-mentioned hydrophilic monomer and structural unit B, which is a hydrophobic monomer derived from glycidyl acrylate or glycidyl methacrylate; and a copolymer composed solely of structural unit A derived from the above-mentioned hydrophilic monomer and structural unit B derived from the above-mentioned hydrophobic monomer. In one embodiment of the present invention, the polymer constituting the lubricating layer is selected from any of the following substances: a polymer consisting only of structural unit A derived from acrylamide, N,N-dimethylacrylamide or N-vinyl-2-pyrrolidone as a hydrophilic monomer; a copolymer substantially consisting of structural unit A derived from the above-mentioned hydrophilic monomer and structural unit B derived from glycidyl acrylate or glycidyl methacrylate as a hydrophobic monomer; and a copolymer consisting only of structural unit A derived from the above-mentioned hydrophilic monomer and structural unit B derived from the above-mentioned hydrophobic monomer.In one embodiment of the present invention, the polymer constituting the lubricating layer is selected from any of the following substances: a polymer composed solely of structural unit A derived from N,N-dimethylacrylamide or N-vinyl-2-pyrrolidone as a hydrophilic monomer; a copolymer substantially composed of structural unit A derived from the above-mentioned hydrophilic monomer and structural unit B derived from glycidyl methacrylate as a hydrophobic monomer; and a copolymer composed solely of structural unit A derived from the above-mentioned hydrophilic monomer and structural unit B derived from the above-mentioned hydrophobic monomer. In one embodiment of the present invention, the polymer constituting the lubricating layer is selected from any of the following substances: a copolymer substantially composed of structural unit A derived from N,N-dimethylacrylamide and structural unit B derived from glycidyl methacrylate; or a copolymer composed solely of structural unit A derived from N,N-dimethylacrylamide and structural unit B derived from glycidyl methacrylate.
[0078] The manufacturing method of the polymer involved in this invention is not particularly limited, and known methods can be applied in the same way or with appropriate modifications. Furthermore, the manufacturing method of the copolymer involved in this invention is not particularly limited, and known methods can be applied in the same way or with appropriate modifications. For example, when the copolymer involved in this invention is a block copolymer, conventionally known polymerization methods such as living radical polymerization, polymerization using macromolecular initiators, and polycondensation can be used. Among these, living radical polymerization or polymerization using macromolecular initiators is preferred from the perspective of easy control over the molecular weight and molecular weight distribution of structural units (sites) derived from hydrophobic monomers and structural units (sites) derived from hydrophilic monomers. As for living radical polymerization, there are no particular limitations; for example, methods described in Japanese Patent Application Publication No. 11-263819, Japanese Patent Application Publication No. 2002-145971, Japanese Patent Application Publication No. 2006-316169, and methods such as atom transfer radical polymerization (ATRP) can be applied in the same way or with appropriate modifications. In addition, in polymerization methods using macromolecular initiators, for example, after preparing a macromolecular initiator containing free radical polymerizable groups such as hydrophobic monomers with epoxy groups and peroxide groups, a block copolymer having structural unit A derived from hydrophilic monomers and structural unit B derived from hydrophobic monomers can be produced by polymerizing the macromolecular initiator, hydrophilic monomers, and polymerization initiators used as needed in a polymerization solvent.
[0079] In the preparation of the copolymer, the mixing ratio of the hydrophilic monomer to the hydrophobic monomer is preferably controlled to obtain the above composition. As the polymerization solvent, it can be appropriately selected from solvents capable of dissolving each monomer. For example, water, dimethyl sulfoxide, chlorobenzene, tetrahydrofuran, etc., can be used; from the viewpoint of monomer solubility, dimethyl sulfoxide, chlorobenzene, and tetrahydrofuran are preferred. In the above polymerization, the polymerization conditions are not particularly limited, as long as the copolymerization is carried out. For example, the polymerization temperature is preferably set to 30–150°C, more preferably 40–100°C. Furthermore, the polymerization time is preferably 30 minutes to 24 hours, more preferably 3 to 15 hours. The polymerization is preferably carried out in a non-reactive atmosphere such as a nitrogen atmosphere or an argon atmosphere.
[0080] In addition, chain transfer agents, polymerization rate regulators, surfactants, water-soluble polymers, water-soluble inorganic compounds (alkali metal salts, alkali metal hydroxides, polyvalent metal salts, and non-reducing alkali metal salt pH buffers, etc.), inorganic acids, inorganic acid salts, organic acids and organic acid salts, and other additives may be used as needed during copolymerization. After polymerization, purification is preferably carried out using conventional purification methods such as reprecipitation, dialysis, ultrafiltration, and extraction.
[0081] From the perspective of solubility in solvents, the weight-average molecular weight of the (copolymer) involved in this invention is preferably 10,000 to 10,000,000. From the perspective of ease of preparation of the coating solution, the weight-average molecular weight of the copolymer is more preferably 30,000 to 5,000,000, and particularly preferably 50,000 to 3,000,000. In this specification, "weight-average molecular weight" is a value determined by gel permeation chromatography (GPC) using polystyrene as a standard.
[0082] As described below, the medical device of the present invention can be manufactured by applying a coating liquid containing the above-described polymer onto a substrate layer and then irradiating it with active energy rays. At this time, electron beams or ultraviolet (UV) rays can be used as active energy rays, but especially when the polymer is crosslinked by electron beam irradiation, a photopolymerization initiator (e.g., benzophenone-based photoinitiator, acetophenone-based photoinitiator) is not required. Therefore, in one embodiment, the lubricating layer preferably contains substantially no photopolymerization initiator or its residues. Here, "the lubricating layer contains substantially no photopolymerization initiator or its residues" means that, relative to the total mass of the lubricating layer, the total content (converted to solid components) of unreacted photopolymerization initiator and the residues of reacted photopolymerization initiator is less than 0.5% by mass (lower limit: 0% by mass), preferably less than 0.1% by mass (lower limit: 0% by mass), and more preferably 0% by mass (the lubricating layer contains no photopolymerization initiator or its residues). It should be noted that the fact that the lubricating layer contains substantially no photopolymerization initiator or its residues can be confirmed, for example, by thermal decomposition GC-MS (gas chromatography-mass spectrometry).
[0083] Other Ingredients In addition to the polymers mentioned above, the lubricating layer may also contain other components. There are no particular restrictions on what constitutes these other components. For example, in the case of medical devices such as catheters intended for insertion into body cavities or tubes, examples include anticancer agents, immunosuppressants, antibiotics, antirheumatic drugs, antithrombotic drugs, HMG-CoA reductase inhibitors, ACE inhibitors, calcium channel blockers, antilipidemic drugs, integrin inhibitors, antiallergic agents, antioxidants, GPIIbIIIa antagonists, retinoids, flavonoids, carotenoids, lipid modifiers, DNA synthesis inhibitors, tyrosine kinase inhibitors, antiplatelet drugs, vascular smooth muscle proliferation inhibitors, anti-inflammatory drugs, biologically derived materials, interferon, and NO production promoters (physiologically active substances). There are no particular restrictions on the amount of these other components added; the commonly used amounts are also applicable. Ultimately, the amount of these other components added is appropriately selected by the attending physician based on the severity of the disease being treated and the patient's weight. Preferably, the lubricating layer does not contain any other components (i.e., the lubricating layer is substantially composed of the aforementioned polymer). Specifically, the content of other components is preferably less than 10% by mass (converted to solid components) relative to the mass of the lubricating layer, more preferably less than 5% by mass (converted to solid components), and particularly preferably the lubricating layer does not contain any other components (i.e., the lubricating layer is composed of the aforementioned polymer).
[0084] Needle-like crystals When observing the surface of the lubricating layer involved in this invention, it is preferable that the surface has few needle-like crystals. Specifically, in a 5000x magnification image of the lubricating layer when it is swollen, the number of needle-like crystals with a length of 1 μm or more on the surface of the lubricating layer is preferably less than 5. Generally, when an operator delivers a medical device to a lesion site in a biological lumen (when the operator slides the medical device in the biological lumen), due to repeated friction between the surface of the lubricating layer and the surface of the biological lumen, a portion of the lubricating layer (the coating) may peel off as particles from the lubricating layer. Therefore, especially under severe conditions where the surface of the lubricating layer easily rubs against the wall of the biological lumen (for example, when repeatedly sliding the medical device to deliver it to the lesion site through a portion of the biological lumen with a small radius of curvature, a portion of the biological lumen with continuous bends, or a portion of the biological lumen with a narrow inner diameter), the coating peels off from the lubricating layer surface of the medical device during operation, and the lubrication maintenance (sliding durability) of the lubricating layer easily decreases. In contrast, when there are fewer than 5 needle-like crystals on the surface of the lubricating layer, the likelihood of the lubricating layer peeling off from the needle-like crystals or the needle-like crystals themselves peeling off from the lubricating layer as a coating (microparticle) when the operator slides the medical instrument through the lumen of the biological body can be reduced. Therefore, under the severe condition of increased scraping between the surface of the lubricating layer and the wall of the biological lumen, the lubrication maintenance (sliding durability) of the lubricating layer can be further improved. From the viewpoint of further improving the lubrication maintenance (sliding durability) of the lubricating layer, in a 5000x magnification observation image of the lubricating layer when it is swollen, the number of needle-like crystals with a length of 1 μm or more observed on the surface of the lubricating layer is more preferably 3 or less, more preferably 1 or less, and particularly preferably 0. It should be noted that the number of needle-like crystals mentioned above is the number of needle-like crystals visible in the image observed by the method described in the [SEM observation of the lubricating layer (when swollen)] section of the embodiment.
[0085] "thickness" The thickness of the lubricating layer (dry film thickness) is, for example, 0.1 to 10 μm, preferably 0.3 to 5 μm, and more preferably about 0.5 to 3 μm.
[0086] Sliding resistance value As described above, the lubricating layer of the present invention exhibits excellent lubricity (smoothness), thus its sliding resistance value is considered low when wet. Specifically, the sliding resistance value obtained from evaluating the sliding resistance value of the lubricating layer can be less than 20 gf. Furthermore, the sliding resistance value obtained from evaluating the sliding resistance value of the lubricating layer is preferably less than 10 gf, more preferably 7.5 gf or less. On the other hand, there is no particular limitation on the lower limit of the sliding resistance value, for example, it can be 0.1 gf or more. It should be noted that the above-mentioned sliding resistance value is a value measured by the method described in the [Sliding Durability Evaluation] section of the embodiment.
[0087] <Methods for Manufacturing Medical Devices> In the medical device of the present invention, the surface of the lubricating layer has a network structure observed in an image of the lubricating layer during swelling, and a plurality of pores surrounded by the network structure, wherein the network structure and the pores satisfy the conditions (1) or (2) described above. Such a medical device can be manufactured, for example, by forming a coating film (precursor layer) containing a polymer on a substrate layer, and then irradiating the coating film (precursor layer) with active energy rays under specific conditions to form a lubricating layer on the substrate layer. By irradiating the coating film (precursor layer) containing the polymer with active energy rays, the polymer forms a cross-linked structure, and the formation of the network structure and pores of the lubricating layer is promoted. At this time, by controlling the density of the cross-linked structure (cross-linking density) according to the irradiation conditions of the active energy rays, the density of the network structure of the lubricating layer can be controlled, and the area of each pore can also be controlled. In addition, as a method for forming the lubricating layer, a method of heating the coating film (precursor layer) under specific conditions can also be used, but from the viewpoint of production efficiency, a method based on active energy rays is preferred.
[0088] There are no particular restrictions on the type of active energy rays or the irradiation conditions, as long as a network structure and pores that meet the above conditions (1) or (2) can be formed. From the viewpoint of effectively promoting the cross-linking reaction of polymers, electron beams or ultraviolet light are preferred as active energy rays.
[0089] Formation of a Lubricating Layer Based on Electron Beam Irradiation In one embodiment, the lubricating layer of the present invention is preferably formed by irradiating a coating (precursor layer) containing a polymer with an electron beam. That is, the lubricating layer is preferably formed by curing with an electron beam (curing the polymer with an electron beam). In the case of forming the lubricating layer by electron beam irradiation, since the polymers crosslink and cure each other in a short time, it is preferred from the viewpoint of production efficiency. In addition, since electron beam irradiation is carried out at room temperature and does not require heating, it can be used suitable for substrates with low heat resistance. In addition, as described later, in the case of ultraviolet irradiation, a photopolymerization initiator is used to carry out the crosslinking reaction efficiently. At this time, the photopolymerization initiator and its residues may remain in the lubricating layer. In contrast, in the case of forming the lubricating layer by electron beam irradiation, since a photopolymerization initiator is not required, the lubricating layer does not contain the photopolymerization initiator and its residues, which can be considered more preferred from the viewpoint of biological safety required for medical devices.
[0090] Therefore, another aspect of the present invention provides a method for manufacturing a medical device, comprising: A coating liquid is applied to at least a portion of a substrate layer to form a precursor layer on at least a portion of the aforementioned substrate layer. The coating liquid comprises a polymer having a structural unit A derived from a hydrophilic monomer and a solvent ((I) precursor layer formation step). The precursor layer is irradiated with an electron beam at an irradiation dose greater than 0 kGy and less than 500 kGy to form a lubricating layer on the substrate layer that swells when in contact with an aqueous solvent ((II-1) Electron beam irradiation process). In the images observed during the swelling of the aforementioned lubricating layer, the surface of the lubricating layer has a mesh structure and multiple pores surrounded by the aforementioned mesh structure. The aforementioned mesh structure and the aforementioned perforations satisfy either condition (1) or condition (2): (1) The average area of the aforementioned holes is 1 μm when viewed from above. 2 The above, and the maximum area is 30μm 2 the following; (2) The average area of the aforementioned holes is 1 μm when viewed from above. 2 The above, and the maximum area is greater than 30μm 2 The average mesh thickness of the aforementioned mesh structure is above 1 μm.
[0091] The preferred embodiments of each process will be described below. It should be noted that the description of the substrate layer, lubricating layer, mesh structure, pores, and conditions (1) and (2) above shall be based on the description of the <Medical Devices> item above.
[0092] (I) Precursor layer formation process In this process, a solution containing a polymer, a solvent, and other components as needed (hereinafter referred to as "coating solution") is prepared. This coating solution is then applied to a substrate layer to form a precursor layer (coating film). The method for applying the coating solution is not particularly limited except for using a solution containing a polymer and a solvent; it can be applied in the same manner as known methods or with appropriate modifications. It should be noted that when the coating solution contains other components, these other components are the same as described above, and therefore their description is omitted here.
[0093] First, a solution (coating solution) comprising a polymer, a solvent, and other components as needed is prepared. Here, there are no particular limitations on the solvent used in the preparation of the coating solution; it can be appropriately selected depending on the type of polymer (and other components if other components are used). From the viewpoint of high solubility, water, acetone, isopropanol (IPA), ethanol, methanol, dichloromethane, chloroform, carbon tetrachloride, tetrahydrofuran (THF), dimethyl sulfoxide, N,N-dimethylformamide, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc., are preferred. One of the above solvents can be used alone, or it can be used as a mixture of two or more solvents.
[0094] The concentration of the polymer in the coating solution is not particularly limited. For example, the polymer concentration in the coating solution is preferably 0.05 to 30% by mass, more preferably 1 to 25% by mass, and particularly preferably 3 to 20% by mass. If the polymer concentration is within the above range, the resulting lubricating layer can fully exert the effects of the present invention. In addition, it is preferable that the desired thickness of the lubricating layer can be easily obtained by one coating, and the viscosity of the solution is within an appropriate range, from the perspective of operability (e.g., ease of coating) and production efficiency. However, even if it exceeds the above range, it can be fully utilized as long as it does not affect the effect of the present invention.
[0095] Next, the coating solution prepared as described above is applied (coated) onto the substrate layer. Here, the substrate layer is the same as described above, so its description is omitted. It should be noted that the substrate layer may be hydrophilicated before applying the coating solution. Examples of methods for hydrophilicating the substrate layer include plasma treatment, electron beam irradiation treatment, and ultraviolet irradiation treatment. The conditions for hydrophilication treatment are appropriately determined depending on the type of substrate layer.
[0096] There are no particular limitations on the method of applying the coating liquid to the surface of the substrate layer. Conventionally known methods such as coating / printing, immersion (dipping), spraying (spraying), spin coating, sponge coating with mixed solution impregnation, bar coating (e.g., wire rod coating), die coating, reverse coating, comma coating, gravure coating, and doctor blade coating can be used. Among these, immersion (dipping), spraying (spraying), and bar coating are preferred.
[0097] In cases where it is difficult to immerse only a portion of the substrate layer in the coating liquid, the surface portion of the substrate layer for which a precursor layer is not required to form can be protected (coated, etc.) beforehand with a suitable, removable (installable and detachable) component or material. The substrate layer is then immersed in the coating liquid, which coats the substrate layer. The protective component (material) for the surface portion of the substrate layer for which a lubricating layer is not required is then removed, thereby forming a precursor layer at the desired surface location of the substrate layer. However, this invention is not limited to these forming methods, and conventionally known methods can be appropriately utilized to form the precursor layer. For example, in cases where it is difficult to immerse only a portion of the substrate layer in the coating liquid, other coating methods can be applied instead of the immersion method (e.g., methods for applying coating liquid to a specified surface portion of a medical device using a sprayer, bar coater, die coater, reverse coater, comma coater, gravure coater, spray coater, doctor blade, etc.). It should be noted that, from the viewpoint of mass production and manufacturing management, the immersion method (dipping method) is preferred.
[0098] The amount of coating liquid applied is preferably selected in such a way that the thickness (dry film thickness) of the resulting lubricating layer is within the range described above.
[0099] Next, the precursor layer formed above is dried as needed to form a precursor layer on the substrate layer. The drying process includes natural drying or heat treatment, but natural drying is preferred. In the case of heat treatment, the conditions are not particularly limited as long as they are sufficient to remove the solvent (enough to form a precursor layer on the substrate layer), and can be appropriately selected depending on the type of solvent. For example, the heat treatment temperature is preferably 10–50°C. Furthermore, the heat treatment time is preferably 1 minute to 5 hours. Under such conditions, the solvent can be removed efficiently, and a precursor layer can be formed on the substrate layer.
[0100] Furthermore, the pressure conditions during the drying process are not restricted in any way; it can be carried out under normal pressure (atmospheric pressure), as well as under pressure or depressurization. Drying methods (apparatus) can include, for example, ovens or vacuum dryers, but in the case of natural drying, no special drying methods (apparatus) are required.
[0101] (II-1) Electron beam irradiation process In this process, the precursor layer formed in (I) above is irradiated with an electron beam under specific conditions to form a lubricating layer. Specifically, the precursor layer formed in (I) above is irradiated with an electron beam at an irradiation dose greater than 0 kGy and less than 500 kGy to form a lubricating layer having a lubricating layer structure that satisfies either condition (1) or condition (2) above.
[0102] In this process, the electron beam irradiation dose to the precursor layer is greater than 0 kGy and less than 500 kGy. When the electron beam irradiation dose to the precursor layer is greater than 500 kGy, the polymer crosslinking reaction proceeds excessively, and the crosslinking density becomes high. As a result, in the lubricating layer, the density of the network structure increases, and the area of the pores decreases, thus reducing the lubricity (smoothness) of the lubricating layer.
[0103] Here, when the polymer constituting the lubricating layer (precursor layer) is the aforementioned copolymer (a copolymer having structural unit A derived from a hydrophilic monomer and structural unit B derived from a hydrophobic monomer having an epoxy group), upon irradiation with an electron beam, the molecular bonds of the hydrophobic sites (especially the epoxy groups) are preferentially cleaved and crosslinked. However, if the electron beam irradiation dose is high, the cleavage of the molecular bonds of the hydrophilic sites in the copolymer also occurs, thus the crosslinking reaction is considered to be excessive. Therefore, when the polymer constituting the lubricating layer (precursor layer) is the aforementioned copolymer, in order to suppress the excessive crosslinking reaction described above and form a suitable lubricating layer structure, it is preferable to reduce the electron beam irradiation dose. Specifically, when the polymer constituting the lubricating layer (precursor layer) is the aforementioned copolymer, the electron beam irradiation dose on the precursor layer is preferably less than 200 kGy, more preferably less than 100 kGy, further preferably less than 100 kGy, particularly preferably less than 50 kGy, and most preferably less than 30 kGy. Furthermore, in order to form multiple free radicals (crosslinking points) by cleaving the molecular bonds of the hydrophobic sites (especially epoxy groups) of the copolymer through electron beam irradiation (in order to improve the film strength of the lubricating layer), the electron beam irradiation dose on the precursor layer is greater than 0 kGy, preferably greater than 5 kGy, and more preferably 10 kGy or more. Therefore, when the polymer constituting the lubricating layer (precursor layer) is the above-mentioned copolymer, the electron beam irradiation dose on the precursor layer is preferably greater than 5 kGy and less than 200 kGy, more preferably greater than 5 kGy and less than 100 kGy, further preferably greater than 5 kGy and less than 100 kGy, particularly preferably 10 kGy or more and 50 kGy or less, and most preferably 10 kGy or more and 30 kGy or less. With such an irradiation dose, the molecular bonds of the hydrophobic sites (especially epoxy groups) of the copolymer can be selectively and efficiently cleaved during electron beam irradiation to form free radicals (crosslinking points), thus enabling the crosslinking reaction of the copolymer to proceed with an appropriate crosslinking density. As a result, a lubricating layer with a suitable lubrication layer structure can be formed, further improving lubricity and durability.
[0104] When the polymer constituting the lubricating layer (precursor layer) is a polymer that does not contain structural unit B derived from hydrophobic monomers (e.g., a polymer composed only of structural unit A derived from hydrophilic monomers), since the cross-linking reaction caused by the hydrophobic sites (especially epoxy groups) described above does not occur, a suitable lubricating layer structure needs to be formed through the cross-linking reaction of the hydrophilic sites. Therefore, when the polymer constituting the lubricating layer (precursor layer) is a polymer that does not contain structural unit B derived from hydrophobic monomers, it is preferable to increase the electron beam irradiation dose in order to promote the cross-linking reaction of the hydrophilic sites and form a suitable lubricating layer structure. Specifically, when the polymer constituting the lubricating layer (precursor layer) is a polymer that does not contain structural unit B derived from hydrophobic monomers, the electron beam irradiation dose of the precursor layer is preferably greater than 100 kGy, more preferably 200 kGy or more, further preferably 300 kGy or more, and particularly preferably 350 kGy or more. Alternatively, in this case, the electron beam irradiation dose of the precursor layer is less than 500 kGy, and may be less than 450 kGy. Therefore, when the polymer constituting the lubricating layer (precursor layer) is a polymer that does not contain structural unit B derived from hydrophobic monomers, the electron beam irradiation dose of the precursor layer is preferably greater than 100 kGy and less than 500 kGy, more preferably 200 kGy or more and less than 500 kGy, further preferably 300 kGy or more and less than 500 kGy, and particularly preferably 350 kGy or more and 450 kGy or less. With such an irradiation dose, the molecular bonds of the hydrophilic sites of the polymer can be broken during electron beam irradiation to form free radicals (crosslinking points), thus allowing the crosslinking reaction of the polymer to proceed at an appropriate crosslinking density. Specifically, with such an irradiation dose, a portion of the ethylene structure constituting the polymer backbone undergoes free radicalization during electron beam irradiation, reacting with free radicals of hydrophilic sites within the same polymer and free radicals of hydrophilic sites of adjacent polymers, thus allowing the crosslinking reaction of the polymer to proceed at an appropriate crosslinking density. As a result, a lubricating layer with an appropriate lubricating layer structure can be formed, further improving lubricity and durability.
[0105] In this process, the electron beam irradiation conditions are appropriately selected based on the type of polymer contained in the lubricating layer (precursor layer). For example, the irradiation temperature is preferably 10–80°C, more preferably 20–40°C. The accelerating voltage is preferably 50–200 kV, more preferably 50–70 kV. Furthermore, electron beam irradiation is preferably carried out in a non-reactive atmosphere such as a nitrogen atmosphere or an argon atmosphere.
[0106] Formation of a Lubricating Layer Based on Ultraviolet Irradiation In other embodiments, the lubricating layer of the present invention can also be formed by irradiating a polymer-containing coating (precursor layer) with ultraviolet light. In the case of forming the lubricating layer by ultraviolet irradiation, the polymer-containing coating liquid further contains a photopolymerization initiator.
[0107] Therefore, another aspect of the present invention provides a method for manufacturing a medical device, comprising: A coating liquid is applied to at least a portion of a substrate layer to form a precursor layer on at least a portion of the aforementioned substrate layer. The coating liquid comprises a polymer having structural unit A derived from a hydrophilic monomer, a photopolymerization initiator, and a solvent ((I) precursor layer formation step). The aforementioned precursor layer is irradiated with ultraviolet light to form a lubricating layer on the aforementioned substrate layer that swells upon contact with an aqueous solvent (II-2 ultraviolet irradiation process). In the images observed during the swelling of the aforementioned lubricating layer, the surface of the lubricating layer has a mesh structure and multiple pores surrounded by the aforementioned mesh structure. The aforementioned mesh structure and the aforementioned perforations satisfy either condition (1) or condition (2) above.
[0108] The preferred embodiments of each process will be described below. It should be noted that the description of the substrate layer, lubricating layer, mesh structure, pores, and conditions (1) and (2) above shall be based on the description of the <Medical Devices> item above.
[0109] (I) Precursor layer formation process In this process, a solution (also called a coating liquid) containing polymer, photopolymerization initiator and solvent, and other components as needed is prepared. The coating liquid is then applied to the substrate layer to form a precursor layer (coating film) on the substrate layer.
[0110] There are no particular limitations on the photopolymerization initiator used at this time, and known photopolymerization initiators can be used. Specifically, examples include carbonyl compounds such as benzophenone compounds and photoreducing pigments. Among these, carbonyl compounds, especially benzophenone compounds, are preferred. Here, the benzophenone compound is not limited to the following substances, and examples include benzophenone, xanthonesone, 9-fluorenone, 2,4-dichlorobenzophenone, methyl o-benzoylbenzoate, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, 5-bis[(4-benzoylbenzyl)oxy]benzene-1,3-disulfonic acid disodium salt, 2,3,4,5,6-pentafluorobenzophenone, decafluorobenzophenone, etc. A single photopolymerization initiator can be used, or two or more can be used in combination. From the viewpoint of easily controlling the crosslinking density, benzophenone or disodium 5-bis[(4-benzoylbenzyl)oxy]benzene-1,3-disulfonic acid is preferred as a photopolymerization initiator.
[0111] There is no particular limitation on the amount of photopolymerization initiator in the coating liquid, as long as it is sufficient for the crosslinking reaction of the polymer to proceed, but it is preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the polymer, more preferably 0.5 to 8 parts by mass, and particularly preferably 1 to 5 parts by mass.
[0112] The concentration of the photopolymerization initiator in the coating solution is preferably adjusted in such a way that the mass ratio of polymer to photopolymerization initiator is within the aforementioned preferred range. For example, the concentration of the photopolymerization initiator in the coating solution is preferably 0.005 to 10% by mass, more preferably 0.05 to 5% by mass. If the concentration of the photopolymerization initiator is within the above range, the crosslinking reaction of the polymer can be sufficiently promoted to form a suitable lubricating layer structure. However, even if the concentration exceeds the above range, it can be fully utilized as long as it does not affect the effect of the present invention.
[0113] In this process, the coating liquid contains a photopolymerization initiator, in addition to the description in "Formation of Lubricating Layer Based on Electron Beam Irradiation".
[0114] (II-2) Ultraviolet Irradiation Process In this process, the precursor layer formed in (I) above is irradiated with ultraviolet light to form a lubricating layer. It should be noted that, in this specification, "ultraviolet light" refers to electromagnetic waves with a wavelength of 10–400 nm. The wavelength of the irradiated ultraviolet light is, for example, 100–400 nm, more preferably 200–400 nm. Examples of means of generating such ultraviolet light include metal halide lamps, high-pressure mercury lamps, low-pressure mercury lamps, mercury-xenon lamps, xenon arc lamps, carbon arc lamps, and excimer lamps.
[0115] In this process, there are no particular restrictions on the irradiation conditions of ultraviolet light on the precursor layer, but it is preferable to set the irradiation intensity and irradiation time in a manner that can promote the cross-linking reaction of the polymer.
[0116] For example, the preferred ultraviolet irradiance is 0.1–100 mW / cm². 2 More preferably 1–50 mW / cm 2 The preferred value is 3–10 mW / cm². 2 In addition, the amount of ultraviolet radiation (cumulative light intensity) is, for example, 300–3000 mJ / cm². 2 Preferably, it is 500–1000 mJ / cm 2 Furthermore, the irradiation time is preferably set in a manner that achieves the aforementioned preferred cumulative light intensity, for example, from 1 second to 30 minutes, preferably from 1 to 5 minutes.
[0117] The above method can be used to manufacture medical devices with a lubricating layer that has excellent lubricity and durability.
[0118] [Uses of medical devices] The medical device of the present invention exhibits excellent lubricity and durability of its lubricating layer. Therefore, when used in contact with bodily fluids, blood, or other aqueous liquids, the surface of the medical device of the present invention is lubricating, improving operability and reducing damage to tissues and mucous membranes. Specifically, examples of medical devices include catheters, stents, and guidewires used intravascularly. That is, in one embodiment of the present invention, the medical device is a catheter, stent, or guidewire. Other examples include the following medical devices.
[0119] (a) Gastric tubes, feeding tubes, and tube feeding tubes, etc., which are inserted or left in the digestive organs through the mouth or nose; (b) Catheters that are inserted or left in the respiratory tract or trachea through the mouth or nose, such as oxygen catheters, oxygen delivery tubes, endotracheal tubes or cuffs, tracheostomy tubes or cuffs, endotracheal suction catheters, etc. (c) Catheters such as urethral catheters, urinary catheters, and urethral balloon catheters that are inserted into or left in place in the urethra or ureter; (d) Catheters such as suction catheters, drainage catheters, and rectal catheters that are inserted into or left in place in various body cavities, organs, and tissues; (e) Catheters inserted into or left in blood vessels, such as indwelling needles, IVH catheters, thermodilution catheters, angiography catheters, vasodilators and dilators or guides, or guidewires and catheterization needles used with these catheters; (f) Artificial trachea, artificial bronchi, etc.; (g) Medical devices used for extracorporeal circulation therapy (artificial lungs, artificial hearts, artificial kidneys, etc.) and their circuits.
[0120] Example The effects of the present invention will be illustrated using the following examples and comparative examples. However, the technical scope of the present invention should not be construed as limited to the following examples, and examples obtained by appropriately combining the technical means disclosed in the various examples are also included within the scope of the present invention. It should be noted that, in the following examples, unless otherwise specified, the operation is carried out at room temperature (25°C). In addition, unless otherwise specified, "%" and "parts" refer to "mass %" and "parts by mass," respectively.
[0121] [Preparation of Coating Samples] Synthesis Example 1: Synthesis of Block Copolymer (p(DMAA-GMA)(12 / 1)) After adding 29.7 g of triethylene glycol dropwise to 72.3 g of adipic dichloride at 50 °C, the hydrochloric acid was removed under reduced pressure at 50 °C for 3 hours to obtain 22.5 g of low-polyester. 4.5 g of methyl ethyl ketone was added to the obtained 22.5 g of low-polyester, and the mixture was added dropwise to a solution consisting of 5 g of sodium hydroxide, 6.93 g of 31% hydrogen peroxide aqueous solution, 0.44 g of dioctyl phosphate as a surfactant, and 120 g of water. The reaction was carried out at -5 °C for 20 minutes. The obtained product was repeatedly washed with water and methanol, and then dried to obtain polyperoxide (PPO) with multiple peroxide groups within the molecule. Next, using benzene as a solvent, 0.5 g of PPO as a polymerization initiator and 9.5 g of glycidyl methacrylate (GMA) as a hydrophobic monomer were stirred and polymerized at 65 °C under reduced pressure for 2 hours. The product obtained after polymerization was reprecipitated with diethyl ether to obtain polyGMA (PPO-GMA) with peroxide groups in the molecule.
[0122] Next, 1.35 g of PPO-GMA (equivalent to 9.5 mmol of GMA) as a polymerization initiator and 11.2 g (113 mmol) of N,N-dimethylacrylamide (DMAA) as a hydrophilic monomer were dissolved in chlorobenzene. The mixture was heated to 80°C and maintained for 7 hours under a nitrogen atmosphere to carry out polymerization. The resulting product was reprecipitated and recovered using cyclohexane to prepare a block copolymer with a DMAA site as the hydrophilic site and a GMA site as the hydrophobic site. Using... 1 ¹H-NMR analysis of the DMAA:GMA molar ratio of the prepared block copolymer confirmed a DMAA:GMA ratio (i.e., the molar ratio of hydrophilic to hydrophobic sites in the block copolymer) of 12:1. Furthermore, the weight-average molecular weight (Mw) of the block copolymer was 1,000,000. Hereinafter, the block copolymer will also be referred to as "p(DMAA-GMA)(12 / 1)".
[0123] Example 1 The block copolymer (p(DMAA-GMA)(12 / 1)) obtained in Synthesis Example 1 was dissolved in acetone to a concentration of 9% by mass to prepare coating solution 1.
[0124] Next, the outer diameter of the polyamide elastomer (Grilflex (registered trademark) ELG6260, manufactured by EMS) (nylon elastomer) was determined. 1.00mm tube substrate (inner diameter) A metal core (approximately 0.6mm in outer diameter) is inserted into the hole. The above-prepared coating solution 1 was dip-coated at a speed of 5 mm / sec to form a precursor layer. After natural drying, the precursor layer (coated surface) was irradiated with an electron beam using an electron beam irradiation device (Hamamatsu Photonics KK, EB-ENGINE (registered trademark) L12978) under nitrogen atmosphere, accelerating voltage of 60 kV, and irradiation dose of 10 kGy to obtain coating sample 1. In the obtained coating sample 1, a lubricating layer containing block copolymer (p(DMAA-GMA)(12 / 1)) was formed on the tube substrate (dry film thickness: approximately 1 μm).
[0125] Example 2 The electron beam irradiation dose in Example 1 was changed to 30 kGy, and the same procedure as in Example 1 was followed to obtain coating sample 2.
[0126] Example 3 The electron beam irradiation dose in Example 1 was changed to 100 kGy, and the same procedure as in Example 1 was followed to obtain coating sample 3.
[0127] Example 4 Coating solution 2 was prepared by dissolving poly(N,N-dimethylacrylamide) (pDMAA) (a homopolymer of N,N-dimethylacrylamide, manufactured by Scientific Polymer, with a weight-average molecular weight (Mw) of 100,000) in acetone at a concentration of 20% by mass.
[0128] Next, the outer diameter of the polyamide elastomer (Grilflex (registered trademark) ELG6260, manufactured by EMS) (nylon elastomer) was determined. 1.00mm tube substrate (inner diameter) A metal core (approximately 0.6mm in outer diameter) is inserted into the hole. The prepared coating solution 2 was dip-coated at a speed of 5 mm / sec to form a precursor layer (0.6 mm). After natural drying, the precursor layer (coated surface) was irradiated with an electron beam using an electron beam irradiation device (Hamamatsu Photonics KK, EB-ENGINE (registered trademark) L12978) under nitrogen atmosphere, accelerating voltage of 60 kV, and irradiation dose of 400 kGy to obtain coating sample 4. In the obtained coating sample 4, a lubricating layer containing polyDMAA (pDMAA) was formed on the tube substrate (dry film thickness: approximately 1 μm).
[0129] Example 5 Polyvinylpyrrolidone (PVP) (a homopolymer of 1-vinyl-2-pyrrolidone (VP), manufactured by Tokyo Chemical Industry Co., Ltd., polyvinylpyrrolidone K90, weight average molecular weight (Mw) = 360,000) was dissolved at 4% by mass in a mixed solvent of water and isopropanol (IPA) (water:IPA = 9:1 (volume ratio)). Disodium 4,5-bis[(4-benzoylbenzyl)oxy]phenyl-1,3-disulfonic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) was dissolved at 0.1% by mass in this mixture to prepare coating solution 3.
[0130] Next, the outer diameter of the polyamide elastomer (Grilflex (registered trademark) ELG6260, manufactured by EMS) (nylon elastomer) was determined. 1.00mm (inner diameter The outer surface of a 0.6 mm diameter tube substrate was irradiated with an electron beam under a nitrogen atmosphere, accelerating voltage of 50 kV, and irradiation dose of 200 kGy to achieve hydrophilication. A metal core (approximately [diameter missing]) was then inserted into the tube substrate. The prepared coating liquid 3 was applied to the hydrophilically treated surface of the tube substrate (0.6 mm) at a speed of 10 mm / sec to form a precursor layer. After natural drying, the coated tube substrate was rotated at 200 rpm while the precursor layer (coated surface) was coated with a coating solution of 6 mW / cm. 2 Irradiation with ultraviolet (UV) light for 2 minutes (cumulative light intensity: 720 mJ / cm²) 2 The resulting coated sample 5 was obtained. At this time, UV irradiation was performed using an EXECURE 4000 (manufactured by HOYA Corporation) and a surface irradiation unit HLL-Q1 (manufactured by HOYA Corporation). In the resulting coated sample 5, a lubricating layer containing polyvinylpyrrolidone (PVP) was formed on the tube substrate (dry film thickness: approximately 2 μm).
[0131] Comparative Example 1 Without irradiating with the electron beam as in Example 1, the same procedure as in Example 1 was followed to obtain coating sample 6.
[0132] Comparative Example 2 The electron beam irradiation dose in Example 1 was changed to 5 kGy, and the same procedure as in Example 1 was followed to obtain coating sample 7.
[0133] Comparative Example 3 The electron beam irradiation dose in Example 1 was changed to 200 kGy, and the same procedure as in Example 1 was followed to obtain coating sample 8.
[0134] Comparative Example 4 The electron beam irradiation dose in Example 1 was changed to 500 kGy, and the same procedure as in Example 1 was followed to obtain coating sample 9.
[0135] For the coating samples 1 to 9 obtained in the above embodiments and comparative examples, the swelling rate of the lubricating layer was determined according to the following method. The results are shown in Table 2 below.
[0136] [Determination of swelling ratio] The swelling ratio of the lubricating layer is calculated using the following formula.
[0137] Swelling rate of lubricating layer (%) = [Swelling film thickness (μm) / Dry film thickness (μm)] × 100 Swelling film thickness (μm) = [(outer diameter of sample during swelling (μm) - outer diameter of sample before swelling (μm))] / 2.
[0138] In the above formula, the dry film thickness of the lubricating layer was measured using a Filmetrics microfilm thickness measurement system (F40, software FILMessure (manufactured by Filmetrics Corporation)). The coating sample was fixed on the stage of the microfilm thickness measurement system, and the film thickness (μm) of the lubricating layer was measured in an environment where the humidity was adjusted to below 30%RH using dry air. The film thickness was also measured at positions rotated 90 degrees, 180 degrees, and 270 degrees from the initial measurement surface, and the average value of the four points was taken as the dry film thickness (μm) of the sample.
[0139] In the above formula, the outer diameter of the sample was measured using a laser diameter measuring machine (LASER SCAN MCROMETER LS, KEYENCE). The coated sample was immersed in RO water for 1 minute, and the outer diameter of the coated sample was measured before and after immersion. The measurement length was set to 50 mm, and measurements were taken at 0.5 mm intervals. These measurements were averaged, and the resulting value was taken as the measured outer diameter (μm) of the coated sample. It should be noted that significant noise caused by non-coating factors such as foreign matter adhesion was excluded when calculating the average value. In addition, when measuring the swelling rate, if at least a portion of the coated sample dissolved and could not be measured, it was determined as "partial dissolution". In the above formula, "outer diameter of the sample before swelling (μm)" is the measured outer diameter of the coated sample before immersion in RO water, and "outer diameter of the sample during swelling (μm)" is the measured outer diameter of the coated sample after immersion in RO water for 1 minute.
[0140] The materials of the substrates of the coating samples 1-9 obtained in the above embodiments and comparative examples, the (copolymer) polymers of the lubricating layers, and the curing methods of the lubricating layers (electron beam irradiation conditions, etc.) are summarized in Table 2 below. It should be noted that in Table 2 below, regarding the curing method, the description "EB "a" kGy ("b" kV) indicates that the irradiation dose during electron beam irradiation is "a" (kGy) and the accelerating voltage is "b" (kV). For example, the electron beam irradiation conditions in Example 1 indicate an accelerating voltage of 60 kV and an irradiation dose of 10 kGy. It should be noted that in Comparative Example 4, no mesh structure was observed in the following SEM observation; therefore, in Table 2 below, the items "Average Area of Holes," "Maximum Area of Holes," "Average Mesh Coarseness," and "Maximum Area / Average Mesh Coarseness" are marked as "-".
[0141] [SEM observation of the lubricating layer (during swelling)] For the coating samples 1-9 obtained in the above embodiments and comparative examples, the surface of the lubricating layer during swelling was observed using a scanning electron microscope (SEM) according to the following steps: 1. Cut each coating sample to a length of approximately 15 mm to obtain a surface observation sample (tube substrate). Immerse the surface observation sample in RO water for at least 5 minutes to allow the lubricating layer to swell. At this time, use a syringe to inject RO water into the inner cavity of the surface observation sample (the inner cavity of the tube substrate) so that the surface observation sample sinks into the RO water; 2. Remove the surface observation sample from the RO water and quickly fix it to the LV (low vacuum) cooled sample holder (manufactured by NEC Corporation) using a carbon ribbon. 3. Add RO water droplets to the surface of the sample to be observed, which is fixed to the cooling sample holder, so that the entire sample is covered with RO water; 4. Quickly immerse the LV cooling sample rack in liquid nitrogen and leave it for about 5 minutes; 5. Remove the LV-cooled sample holder from the liquid nitrogen and quickly transfer it into the SEM (JSM-IT800SHL manufactured by NEC Corporation) in which the chamber vacuum level has been set to 30 Pa in LV mode. 6. Place the sample inside the SEM for about 1 hour to allow the chilled water (chilled water obtained by freezing RO water injected to cover the sample for observation) to sublimate; 7. Remove the LV cooling sample holder from the SEM and fix the sample for surface observation onto the standard SEM sample stage; 8. Osmium coating (approximately 4 nm thick) was performed on the above-mentioned surface observation samples using an osmium coating machine (HPC-20 manufactured by Vacuum Device Inc.); 9. The outer surface of the above-mentioned surface observation sample was observed by SEM in high vacuum mode (around E-3 to E-4 Pa) with a field of view of 5000x.
[0142] The SEM image (5000x magnification) obtained through the above SEM observation is shown below. Figures 1-9 The SEM observation results showed that no needle-like crystals (needle-like crystals larger than 1 μm) were observed in any sample at 5000x magnification (the number of needle-like crystals was 0). Here, needle-like crystals could potentially increase the amount of particles (coating sheets) that detach from the surface of the lubricating layer when the medical device slides. According to the medical device and its manufacturing method of the present invention, since the generation of needle-like crystals is suppressed, it can be considered that this also greatly reduces the amount of particles (coating sheets) that might detach from the surface of the lubricating layer.
[0143] [Network Structure Analysis] For coating samples 1-9, the network structure (network thickness, pore area, etc.) of the lubricating layer was analyzed based on the SEM images (5000x magnification) obtained through the above steps. The analysis of pores and network thickness was performed as follows. The results are shown in Table 2 below. It should be noted that in the above [SEM observation of the lubricating layer (when swollen)], the lubricating layer of the surface observation sample was observed after freeze-drying. The lubricating layer of the surface observation sample was maintained in its swollen state during SEM observation through freeze-drying. Therefore, in the above [SEM observation of the lubricating layer (when swollen)], the network thickness and pore area (average area, maximum area) in the freeze-dried lubricating layer did not change from the swollen lubricating layer. Therefore, the analysis results of the network structure (network thickness, pore area, etc.) based on the SEM images obtained through the above steps are used as the analysis results of the network structure in the swollen lubricating layer.
[0144] (Analysis of the perforation) Using image processing software (ImageJ; US National Institutes of Health), analyze the hole sizes in the above SEM images (5000x magnification) according to the following steps to determine the average and maximum area of the holes: 1. Open the SEM image to be analyzed (5000x magnification), and select the area of the SEM image excluding the measurement conditions and scale (specifically, the area of the SEM image excluding the measurement conditions and scale). Figures 1-9 The range of the SEM image shown is used as the analysis range (vertical 19.2 (μm) × horizontal 25.6 (μm)).
[0145] 2. Next, select the "Adjust" tab and then the "Threshold" tab, and click the "Apply" button to create binarized images of the holes (black) and the mesh structure (white). The resulting binarized image (corresponding to the SEM image in Example 2) is illustrated below. Figure 10 .
[0146] 3. Next, after selecting the analysis range again in step 1, click the "Process" tab and then "Find Edges" to perform edge processing on the boundary between the holes and the mesh structure. (Regarding...) Figure 10 The SEM image, with the edge-processed image shown above as an example. Figure 11 .
[0147] 4. Next, select the "Analyze" tab, then select "Analyze Particles," and click the "OK" button. This will perform analysis on particles with a size of 0.1 μm. 2 The above is a pore analysis. Other analytical conditions for analyzing particles are selected as follows.
[0148] • Size: 0.10 - infinity (μm) 2 ) • Circularity: 0.00-1.00 • Show: Outline Other selected items - Display results -Clear results - Add to Manager - Includes holes -Overlay 5. Based on the above analysis results, calculate the average area and maximum area of the hole.
[0149] (Analysis of net thickness) 1. Similarly, the edge processing in step 3 of the above hole analysis was performed to create an edge-processed image.
[0150] 2. Divide the edge-processed image into 9 parts (divided into 3 rows × 3 columns). In each part, arbitrarily measure 1 point (a total of 9 points) the size (mesh thickness) between the holes (mesh structure) in each part.
[0151] 3. Calculate the arithmetic mean of the mesh thickness in each partition obtained in step 3 above, and use it as the average mesh thickness.
[0152] [Sensory Evaluation] Sensory evaluations were performed on coating samples 1 to 9 obtained in the above embodiments and comparative examples according to the following steps. The results are shown in Table 2 below.
[0153] The lubricating layer (coated surface) of coating samples 1-9 was immersed in RO water. After 1 minute, while still immersed, the lubricating layer was pinched with the fingertip and rubbed back and forth 30 times along the length of the sample with the fingertip at a width of approximately 5 cm. The smoothness (lubricity) and durability at this point were evaluated according to the evaluation criteria in Table 1 below. Smoothness (lubricity) was categorized based on the feel of the second rub according to the following evaluation criteria, and durability was categorized based on the change in smoothness after 30 rubs. It should be noted that the intensity and speed of friction were kept as consistent as possible among the samples.
[0154] [Table 1] [Sliding Durability Evaluation] For the coating samples 1 to 9 obtained in the above embodiments and comparative examples, the sliding durability (lubrication maintenance) was evaluated according to the following method. The results are shown in the "OR20 times (gf)" item in Table 2 below.
[0155] In the evaluation, the sliding resistance value of the lubricating layer of each coated sample was determined using an Oak River sliding tester (manufactured by Oak River Technology A PaR Systems Company, DL1000) following the steps described below.
[0156] The container was filled with RO water, and each coating sample was fixed in an Oak River sliding tester, with the test area of the lubricating layer (coated surface) immersed in the RO water. After immersing the coating sample in the RO water for 1 minute, a pair of silicone terminals (13mm × 32mm) of the Oak River sliding tester were brought close together, and the test area of the coating sample was clamped under a load of 500gf. Then, while applying a clamping force of 500gf to the silicone terminals, the coating sample was moved at a sliding distance of 50mm and a sliding speed of 10mm / sec, and the same part of the coating sample was repeatedly slid along the vertical direction 20 times. At this time, the sliding resistance value (gf) was measured when the sample was lifted vertically for the 20th time. It should be noted that before measuring the sliding resistance value, a metal core was inserted into the inner cavity of the coating sample (tube substrate).
[0157] [Table 2] As can be seen from the results in Table 2, compared with the coating samples 1, 2, 6 and 7 of the comparative examples, the coating samples 3 to 5, 8 and 9 of the embodiments can simultaneously achieve lubricity (smoothness) and durability.
[0158] First, the relationship between the analysis results of the network structure and the evaluation results was studied as follows: Sufficient lubricity (smoothness) could not be obtained in coating samples 6 and 7 of Comparative Examples 3 and 4, while sufficient lubricity (smoothness) was obtained in other coating samples. This can be attributed to the fact that the average area of the pores in the lubricating layers of Comparative Examples 3 and 4 (coating samples 6 and 7) is less than 1 μm. 2 (In coating sample 7, such as) Figure 7 As shown, in the 5000x magnification image, the network structure forms so densely that it is visually indistinguishable, appearing as if no network structure has formed. Under such conditions, sufficient water (water molecules) cannot be absorbed into the pores, making swelling difficult. In contrast, in the coating samples other than 6 and 7, the average pore area of any sample is 1 μm². 2 The above allows for the absorption of a sufficient amount of water (water molecules) within the pores. As a result, the lubricating layer can be considered to have good swelling properties and excellent lubricity (smoothness).
[0159] Furthermore, although the coating samples 1 and 2 of Comparative Examples 1 and 2 exhibited good lubricity (smoothness) in their lubricating layers, sensory evaluations regarding durability revealed rapid peeling and poor durability of the lubricating layers. In contrast, other coating samples (coating samples 3-9) yielded lubricating layers with good durability. This can be attributed to the larger maximum area of the pores (greater than 30 μm) in coating samples 1 and 2. 2 This allows the lubricating layer to easily absorb water (water molecules), resulting in excellent lubricity (smoothness). On the other hand, the average mesh size in the mesh structure is less than 1 μm. Due to the excessively fine mesh size, the mesh structure is prone to damage due to slippage, reducing the durability of the lubricating layer. Therefore, it was determined that the maximum area in the pores is greater than 30 μm. 2 In the case of setting the average mesh thickness to 1 μm or more (i.e., satisfying condition (2)), not only can the lubricity (smoothness) of the lubricating layer be improved, but also its durability can be improved.
[0160] Furthermore, although the average mesh size of coating samples 5 and 6 in Example 3 and Comparative Example 3 was less than 1 μm, these coating samples also exhibited good durability. This can be attributed to the relatively small maximum area of the pores in coating samples 5 and 6 (30 μm). 2(The following is an example of this). Therefore, the mesh structure is densely formed, and it is speculated that even with a relatively fine mesh itself, a lubricating layer with sufficient durability can be formed. (However, as mentioned above, Comparative Example 3 (coated sample 6) has an average pore area of less than 1 μm.) 2 Therefore, good lubricity (smoothness) cannot be achieved. Furthermore, when comparing the coating samples 3-5 of Examples 1-3 in Table 2, it can be considered that coating samples 3 and 4 are superior to coating sample 5 in terms of lubricity (smoothness) and durability (especially superior lubricity). Based on this result, it can be considered that when the maximum area of the pores is larger and the mesh thickness is coarser, the lubricating layer can maintain excellent lubricity (smoothness) and exhibit good durability. That is, it can be considered that satisfying condition (2) is more preferable than satisfying condition (1) of the present invention.
[0161] Next, the formation conditions (curing method) of the lubricating layer were discussed as follows: For coating samples 1-7, they were prepared under the same conditions, except for the electron beam irradiation conditions during curing. See Table 2 and... Figures 1-7 As shown, it was determined that when the lubricating layer is cured by electron beam irradiation, the mesh thickness of the network structure increases with the irradiation dose, and tends to decrease when the irradiation dose exceeds 30 kGy and reaches approximately 100 kGy. When the lubricating layer is formed by electron beam irradiation, if the electron beam irradiation dose to the precursor layer (coating surface) increases, the crosslinking reaction caused by the epoxy groups (derived from GMA) contained in the copolymer (p(DMAA-GMA)(12 / 1)) increases, and the crosslinking density of the lubricating layer increases. Therefore, it is believed that when the electron beam irradiation dose to the precursor layer (coating surface) is 100 kGy, compared with the electron beam irradiation doses of 10 kGy and 30 kGy, the crosslinking reaction caused by the epoxy groups (derived from GMA) contained in the copolymer (p(DMAA-GMA)(12 / 1)) increases, thus increasing the crosslinking density of the lubricating layer and decreasing the average and maximum pore areas. Therefore, it is believed that as the crosslinking density of the lubricating layer increases, the average web thickness also decreases. Furthermore, it is believed that when the electron beam irradiation dose to the propagator layer (coated surface) is 0 kGy or 5 kGy, compared to when the electron beam irradiation dose to the propagator layer (coated surface) is 10 kGy, the crosslinking reaction caused by the epoxy groups (derived from GMA) contained in the copolymer (p(DMAA-GMA)(12 / 1)) is not fully carried out, resulting in a lower crosslinking density of the lubricating layer and thus a smaller average web thickness.
[0162] Furthermore, when the electron beam irradiation dose to the precursor layer (coated surface) exceeds 100 kGy, the crosslinking reaction of the copolymer further increases, thus further increasing the crosslinking density of the lubricating layer. Therefore, it is speculated that when the electron beam irradiation dose to the precursor layer (coated surface) is 500 kGy, in the 5000x magnification observation image of the lubricating layer during swelling, the average area of the pores on the surface of the lubricating layer further decreases, resulting in a smoother appearance.
[0163] Therefore, by taking this tendency into account and appropriately adjusting the electron beam irradiation amount, it is possible to control the area of the pores and the mesh thickness in the mesh structure of the lubricating layer.
[0164] Furthermore, in coating sample 8 of Example 4, the polymer (DMAA homopolymer) forming the lubricating layer differs from the aforementioned copolymer (p(DMAA-GMA)(12 / 1)) and does not possess epoxy groups. Therefore, although intramolecular and / or intermolecular crosslinking reactions based on electron beam irradiation also occur in coating sample 8, its reactivity is low (lower than epoxy groups). Therefore, it is considered that the electron beam irradiation dose required to form a suitable lubricating layer structure is greater compared to the case using the aforementioned copolymer. If the electron beam irradiation dose to the precursor layer (coating surface) is increased, it may cause damage to the substrate layer. Therefore, compared to coating sample 8 of Example 4, coating samples 3-5 of Examples 1-3 are preferred because they can cure the polymer of the precursor layer (coating surface) with a lower electron beam irradiation dose.
[0165] Furthermore, while the coating sample 9 of Example 5 underwent UV-based curing, it was able to form a suitable network structure similar to that obtained with electron beam irradiation, resulting in a lubricating layer with excellent lubricity (smoothness) and durability. The coating sample 9 of Example 5 requires a photopolymerization initiator to cure the polymer in the precursor layer (coating surface). Therefore, the coating sample 9 of Example 5 may have unreacted photopolymerization initiator residues remaining in the lubricating layer. Therefore, compared to the coating sample 9 of Example 5, the coating samples 3-5 of Examples 1-3 are preferred from the viewpoint of biological safety requirements for medical devices because they can cure the copolymer in the precursor layer (coating surface) without using a photopolymerization initiator.
[0166] This application is based on Japanese Patent Application No. 2024-052926 filed on March 28, 2024 and Japanese Patent Application No. 2025-046740 filed on March 21, 2025, the disclosures of which are incorporated herein by reference in their entirety.
Claims
1. Medical equipment, which includes: Substrate layer, and A lubricating layer supported on at least a portion of the substrate layer and swelling upon contact with an aqueous solvent. The lubricating layer comprises a polymer having structural unit A derived from a hydrophilic monomer. In the observed images of the lubricating layer during swelling, the surface of the lubricating layer has a mesh structure and multiple pores surrounded by the mesh structure. The mesh structure and the perforated portion satisfy either condition (1) or condition (2): (1) The average area of the hole is 1 μm when viewed from above. 2 The above, and the maximum area is 30μm 2 the following; (2) The average area of the hole is 1 μm when viewed from above. 2 The above, and the maximum area is greater than 30μm 2 The average mesh thickness of the mesh structure is above 1 μm.
2. The medical device as described in claim 1, wherein, The average area of the pores when viewed from above is 1–10 μm. 2 The ratio of the maximum area of the aperture relative to the average mesh thickness of the mesh structure (the maximum area of the aperture (unit: μm)). 2 The average thickness (in μm) of the mesh structure is 20 to 50.
3. The medical device as described in claim 1, wherein, The average area of the pores when viewed from above is 3–10 μm. 2 .
4. The medical device as described in claim 1, wherein, The average area of the pores when viewed from above is 3–10 μm. 2 And the maximum area is greater than 30μm 2 And it is 100μm 2 The following is a ratio of the maximum area of the aperture to the average mesh thickness of the mesh structure (the maximum area of the aperture (unit: μm)). 2 The average thickness (in μm) of the mesh structure is 20 to 50.
5. The medical device as described in claim 1, wherein, In a 5000x magnification image of the lubricating layer during swelling, there are fewer than 5 needle-like crystals with a length of 1 μm or more on the surface of the lubricating layer.
6. The medical device as described in claim 1, wherein, The structural unit A derived from the hydrophilic monomer is a structural unit derived from at least one monomer selected from the group consisting of acrylic acid, acrylamide, N-methylacrylamide, N,N-dimethylacrylamide, N-ethylacrylamide, N,N-diethylacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethylacrylamide, 2-acrylamido-2-methylpropanesulfonic acid, N-(2-hydroxyethyl)acrylamide, N-(2-hydroxypropyl)acrylamide, N-(2-hydroxybutyl)acrylamide, N-vinyl-2-pyrrolidone, polyethylene glycol monoacrylate, polyethylene glycol monomethacrylate, alkoxy polyethylene glycol monoacrylate, and alkoxy polyethylene glycol monomethacrylate.
7. The medical device as described in claim 1, wherein, The lubricating layer comprises a copolymer having structural unit A derived from a hydrophilic monomer and structural unit B derived from a hydrophobic monomer having an epoxy group.
8. The medical device as described in claim 7, wherein, The structural unit B derived from the hydrophobic monomer having an epoxy group is a structural unit derived from at least one monomer selected from the group consisting of glycidyl acrylate, glycidyl methacrylate, 3,4-epoxycyclohexyl methyl acrylate, 3,4-epoxycyclohexyl methyl methacrylate, β-methyl glycidyl acrylate and β-methyl glycidyl methacrylate.
9. The medical device as described in claim 7, wherein, The copolymer contains structural units A derived from hydrophilic monomers in a ratio of 5 to 50 moles relative to 1 mole of structural unit B derived from the hydrophobic monomer having an epoxy group.
10. The medical device as claimed in claim 1, wherein, The sliding resistance value obtained from the evaluation of the sliding resistance value of the lubricating layer is less than 20gf.
11. The medical device as claimed in claim 1, wherein, The lubricating layer does not contain photopolymerization initiators or their residues.
12. The medical device as claimed in claim 1, wherein, The lubricating layer is formed by curing with an electron beam.
13. The medical device as claimed in claim 1, wherein, The medical device is a catheter, stent, or guidewire.
14. A method for manufacturing medical devices, comprising: A coating liquid is applied to at least a portion of a substrate layer to form a precursor layer on at least a portion of the substrate layer. The coating liquid comprises a polymer having structural unit A derived from a hydrophilic monomer, and a solvent. The precursor layer is irradiated with an electron beam at an irradiation dose greater than 0 kGy and less than 500 kGy, forming a lubricating layer on the substrate layer that swells upon contact with an aqueous solvent. In the observed images of the lubricating layer during swelling, the surface of the lubricating layer has a mesh structure and multiple pores surrounded by the mesh structure. The mesh structure and the perforated portion satisfy either condition (1) or condition (2): (1) The average area of the hole is 1 μm when viewed from above. 2 The above, and the maximum area is 30μm 2 the following; (2) The average area of the hole is 1 μm when viewed from above. 2 The above, and the maximum area is greater than 30μm 2 The average mesh thickness of the mesh structure is above 1 μm.
15. The manufacturing method as described in claim 14, wherein, The precursor layer is irradiated with an electron beam at an irradiation dose greater than 5 kGy and less than 200 kGy.
Citation Information
Patent Citations
Medical tool, with lubricative surface in wet state and manufacture therefor
JP1996033704A
Solid with grafted surface and its production
JP1999263819A
Nano structural functional material
JP2002145971A
Solid lubricating material
JP2006316169A
Information processing device, information processing method, information processing program, and recording medium
JP2024052926A
